Large-scale synthesis of oxidative dehydrogenation catalysts

JP2024509101A5Pending Publication Date: 2025-02-18NOVA CHEM (INT) SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023551719
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-26
Filing Date
2022-02-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The high energy consumption and coke formation issues in steam cracking processes for converting alkanes to olefins, along with the need for scalable production of oxidative dehydrogenation (ODH) catalysts, pose challenges for commercial polymer production.

Method used

Development of large-scale synthesis methods for ODH catalysts comprising molybdenum, vanadium, tellurium, niobium, and oxygen, with controlled sulfur content, using hydrothermal reaction and extensive washing to produce a precatalyst, followed by air treatment and calcination to enhance catalyst performance.

Benefits of technology

The method enables the production of high-performance ODH catalysts with reduced water usage and effective removal of contaminants, improving catalyst stability and selectivity for olefin production without coke formation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Catalysts and methods for large scale production of catalysts are provided. Exemplary catalyst compositions include molybdenum, vanadium, tellurium, niobium, and oxygen. In the catalyst composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.01 to 1:0.40. Oxygen is present in an amount to at least satisfy the valence of the metal oxides present, and the composition includes less than 1.0 wt.% sulfur.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This disclosure relates generally to oxidative dehydrogenation (ODH) catalysts and systems, and more specifically to the large-scale synthesis of ODH catalysts. [Background technology]

[0002] Olefins, such as ethylene, propylene, and butylene, are the basic building blocks of a variety of commercially valuable polymers. Naturally occurring sources of olefins do not exist in commercial quantities, so polymer manufacturers rely on methods to convert more abundant lower alkanes into olefins. The method of choice for commercial-scale producers today is steam cracking, a highly endothermic process that briefly exposes alkanes diluted with steam to temperatures of at least 800 °C. The fuel demand to generate the required temperatures, and the need for equipment that can withstand them, significantly increase overall costs. In addition, high temperatures promote coke formation, which accumulates in the system, necessitating costly periodic reactor shutdowns for maintenance and coke removal.

[0003] Oxidative dehydrogenation (ODH) is an alternative to steam cracking that is exothermic and produces little or no coke. In ODH, lower alkanes such as ethane are mixed with oxygen in the presence of a catalyst and optionally an inert diluent (such as carbon dioxide, nitrogen, or steam) at temperatures as low as 300°C to produce the corresponding alkenes. A variety of other oxidation products, such as carbon dioxide and acetic acid, may be produced in this process. As the ODH process becomes more commercialized, research is needed to scale up the production of commercial-scale catalysts. Summary of the Invention

[0004] Exemplary embodiments described in the Examples herein provide a catalyst composition comprising molybdenum, vanadium, tellurium, niobium, and oxygen, wherein the molar ratio of molybdenum to vanadium is from 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.40, the oxygen is present in an amount at least sufficient to satisfy the valence of any metal oxides present, and the composition comprises less than 1.0 wt.% sulfur.

[0005] Another exemplary embodiment described in the Examples herein provides a pre-calcined catalyst composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. In the catalyst composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.05 to 1:0.40. The oxygen is present in an amount that satisfies at least the valence of the metal oxides present, and the sulfur, if present, comprises 0.001% to 0.25% by weight of the composition. The composition is prepared by a method comprising hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-washed ODH catalyst precursor comprising greater than 0.5% by weight sulfur, and washing the pre-washed ODH catalyst precursor with a solution comprising water to provide an ODH catalyst precursor comprising less than 1.0% by weight sulfur.

[0006] Another exemplary embodiment described in the examples herein provides a method for preparing a catalyst composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and optionally sulfur. In the catalyst composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.05 to 1:0.40. The oxygen is present in an amount that satisfies at least the valence of the metal oxides present, and sulfur, if present, accounts for less than 0.25 wt.% of the composition. The method includes hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-washed catalyst composition comprising more than 0.5 wt.% sulfur, and washing the pre-washed catalyst composition with a solution comprising a polar solvent to provide a catalyst composition comprising less than 0.25 wt.% sulfur.

[0007] Another exemplary embodiment described in the Examples herein provides a catalytic material comprising molybdenum, vanadium, tellurium, niobium, and oxygen, wherein the molar ratio of molybdenum to vanadium is 1:0.12 to 1:0.49, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.01 to 1:0.30, the oxygen is present in an amount at least sufficient to satisfy the valence of any metal oxide present, and sulfur, if present, comprises less than 0.01 weight percent of the catalytic material.

[0008] Another exemplary embodiment described in the Examples herein provides a method for preparing a catalytic material comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. The method includes hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-cleaned composition comprising greater than 0.5% by weight of sulfur. The method includes washing the pre-cleaned composition with a solution comprising a polar solvent to provide a catalytic composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. In the catalytic composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.01 to 1:0.40. Oxygen is present in the catalytic composition in an amount that at least satisfies the valence of the metal oxides present. Sulfur accounts for less than 0.25% by weight of the composition. The method includes calcining a catalyst composition to provide a catalyst material, wherein the molar ratio of molybdenum to vanadium is from 1:0.12 to 1:0.49, the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.30, oxygen is present in an amount at least to satisfy the valences of any metal oxides present, and sulfur, if present, comprises less than 0.01 weight percent of the catalyst material. [Brief description of the drawings]

[0009] [Figure 1] 1A and 1B are block diagrams of oxidative dehydrogenation systems for the oxidative dehydrogenation of light hydrocarbons, according to an embodiment. [Diagram 2] FIG. 2 is a diagram of a chemical complex according to some embodiments. [Diagram 3] FIG. 3 is a diagram of a chemical complex according to some embodiments. [Figure 4] FIG. 4 is a schematic diagram of a microreactor unit (MRU) described in the Examples. [Diagram 5] FIG. 5 is a fabrication drawing of the thermocouples in the microreactor unit (MRU) showing the locations of the six thermocouple measurement points. [Figure 6] FIG. 6 is a plot showing the infrared spectrum of a poorly washed catalyst composition overlaid on the infrared spectrum of a thoroughly washed catalyst composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Oxidative dehydrogenation (ODH) is commonly used to form ethylene or other α-olefins from ethane. The embodiments described herein provide a process for the preparation of large batches, e.g., 2 kg or more, of a catalyst system for oxidative dehydrogenation. The catalyst includes molybdenum (Mo), vanadium (V), tellurium (Te), niobium (Nb), and oxygen (O). MoVTeNbO for oxidative dehydrogenation of alkanes x Multicomponent metal oxide catalysts such as are known. Such catalysts are typically prepared by mixing solutions of metals, then precipitating metal oxide precursors from the mother liquor, and then calcining the dried precursor to form the catalyst. The calcined catalysts exhibit improved catalytic properties, such as, for example, enhanced selectivity to the desired olefin products and improved process stability, compared to the uncalcined precursors. As a result, multicomponent metal oxide catalysts are typically calcined before being used in process applications. However, uncalcined catalysts exist in a "multipotent" state. Depending on the calcination induction procedure used, they may be differentiated into various potential fixed chemical states. Thus, if the catalyst calcination step is not performed under the correct conditions or if a prior work-up step is missing, the properties of the catalyst may be adversely affected.

[0011] One of the major problems associated with scale-up is the filtering of the catalyst. The filtering step separates the solid catalyst from the aqueous solution and washes away contaminating by-product salts, such as sulfur and nitrogen compounds. If salts remain in the catalyst, they may degrade the catalyst during calcination, reducing its performance. Thus, large amounts of water, about 29 L of water per kg of catalyst, are typically used to wash away the salts. However, it is often difficult to remove the salts while preventing some of the solid catalyst particles from being wasted during filtration. The process provided in the examples herein allows the synthesis of MoVTeNbO at large scale (e.g., greater than about 2 Kg) without using as much water (e.g., about 12 L) per kg of catalyst as conventional processes. x It enables the production of ODH catalysts, which can effectively remove contaminating salts without wasting a portion of the solid catalyst particles.

[0012] The technology described herein includes an air treatment step using stagnant air prior to calcination, which can reduce the amount of water used for filtration and washing. A flowing air treatment step has been used as part of a high temperature (550-650°C) inert gas (nitrogen) calcination. However, the air treatment described herein involves treatment with stagnant air at 250°C in an oven, rather than flowing air over the catalyst bed in the calcination unit. The catalyst bed depth can be 5-12 cm to allow for large loadings during air treatment. As used herein, a depth of about 980 cm is used for large loadings. 2 With a small loading, it has a surface area of ​​approximately 104 cm 2 The surface area is less than 100 nm. The amounts of material at higher loadings are based on examples (see, for example, Table 3.6). By comparing these results with Catalytic Material 3.X (Table 4.3) and Catalytic Material 4.X (Table 5.4), the differences due to the scale examples and the requirements to meet the S specifications can be seen.

[0013] As used herein, the term "catalytic material" refers to a material that includes an active catalyst capable of promoting the oxidative dehydrogenation of ethane to ethylene, for example, on a support. The catalytic material can be a plurality of particles or a formed catalytic material. Non-limiting examples of formed catalytic materials include extruded catalytic materials, pressed catalytic materials, and cast catalytic materials. Non-limiting examples of pressed and cast catalytic materials include pellets, such as tablets, oval, and spherical particles.

[0014] As used herein, the term "catalyst composition" generally refers to the active catalytic portion of a catalytic material. The catalyst composition is generally processed in further steps to form a catalytic material.

[0015] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. It is to be understood that the numerical ranges set forth herein are intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges therebetween, including the stated minimum value of 1 and the stated maximum value of 10, i.e., the minimum value is equal to or greater than 1 and the maximum value is equal to or less than 10. Because the disclosed numerical ranges are continuous, every value between the minimum and maximum values ​​is included. Unless otherwise indicated, the various numerical ranges specified in this application are approximations.

[0016] As used herein, the term "alkane" refers to acyclic saturated hydrocarbons. In most cases, alkanes are composed of hydrogen and carbon atoms arranged in a linear structure in which all carbon-carbon bonds are single bonds. The general chemical formula for alkanes is C n H 2n+2In some embodiments, alkane refers to one or more of ethane, propane, butane, pentane, hexane, octane, decane, and dodecane. In particular embodiments, alkane refers to ethane and propane, and in some embodiments, ethane.

[0017] As used herein, the term "alkene" refers to an unsaturated hydrocarbon containing at least one carbon-carbon double bond. In many embodiments, alkene refers to an alpha olefin. In some embodiments, alkene refers to one or more of ethylene, propylene, 1-butene, butadiene, pentene, pentadiene, hexene, octene, decene, and dodecene. In particular embodiments, alkene refers to ethylene and propylene, and in some embodiments, ethylene.

[0018] As used herein, the term “alpha olefin” or “α-olefin” refers to a compound of the chemical formula C x H 2x Alpha olefins refers to a family of organic compounds that are alkenes (also known as olefins) and are distinguished by the presence of a double bond in the primary or alpha (α) position. In some embodiments, alpha olefins refers to one or more of ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, and 1-dodecene. In particular embodiments, alpha olefins refers to ethylene and propylene, and in some embodiments, ethylene.

[0019] As used herein, the term "essentially oxygen-free" means that the amount of oxygen remaining in the process stream after the one or more ODH reactors, and in many embodiments after the second reactor described herein, is sufficiently low so as not to present a flammable or explosive hazard to downstream process streams or equipment.

[0020] As used herein, the term "fixed bed reactor" refers to one or more reactors in series or parallel, often containing cylindrical tubes packed with catalyst pellets, in which reactants flow through the fixed bed and are converted to products. The catalyst within the reactor can have several configurations, including, but not limited to, one large bed, several horizontal beds, several parallel packed tubes, and multiple beds within their own shell.

[0021] As used herein, the term "fluidized bed reactor" refers to one or more reactors in series or parallel, often containing a fluid (gas or liquid) that passes through a solid particulate catalyst, which may be in the form of tiny globules, at a velocity sufficient to suspend the solids and cause them to behave as if they were a fluid.

[0022] As used herein, the term "monomer" refers to a small molecule containing at least one double bond, which reacts in the presence of a free radical polymerization initiator to chemically combine with other monomers to form a polymer.

[0023] As used herein, the term "moving bed reactor" refers to a reactor in which catalyst material flows with the reactants and is subsequently separated from the exit stream and recycled.

[0024] As used herein, the term "MoVOx catalyst" refers to a catalyst having an empirical formula of Mo 6.5-7.0 V3O d where d is a number that at least satisfies the valence of the oxide; 6.25-7.25 V3O d where d is a number that satisfies the valence of the oxide, or a combination thereof.

[0025] As used herein, the term "olefinic monomer" includes, but is not limited to, α-olefins, and in certain embodiments, ethylene, propylene, 1-butene, 1-hexene, 1-octene, and combinations thereof.

[0026] In this disclosure, "active oxygen" means oxygen that is captured by the oxidative dehydrogenation catalyst and is available for the oxidative dehydrogenation reaction to be removed from the catalyst.

[0027] In this disclosure, the term "active oxygen depleted" when referring to the catalyst in the pre-reactor does not mean absolute oxygen depletion. Rather, it means that the level of active oxygen remaining in the catalyst is sufficiently low to be less than 25%, preferably less than 15%, and most preferably less than 10% of the maximum amount of oxygen that was incorporated into the catalyst. After releasing the active oxygen, the catalyst is composed of metal oxides that do not release oxygen.

[0028] By substantially saturated with active oxygen it is meant that at least 60%, preferably greater than 70%, and most preferably greater than 85% of the active oxygen is complexed with the oxidative dehydrogenation catalyst.

[0029] As used herein, the term "substantially acetylene-free" means that the amount of acetylene remaining in the process stream after the one or more ODH reactors, and in many embodiments after the second reactor described herein, if any, is not detectable or is zero vppm using the analytical techniques described herein.

[0030] As used herein, the term "swing bed reactor configuration" is a gas phase reactor system in which a first vessel effectively operates as a reactor and a second vessel effectively operates as a regenerator for regenerating the catalyst system. This configuration can be used with fixed bed and fluidized bed ODH reactors.

[0031] In some embodiments disclosed herein, the extent to which carbon monoxide is produced during the ODH process can be mitigated by converting it to carbon dioxide, which can act as an oxidant. The process can be operated to control the emission of carbon dioxide from the process to a desired level. Using the methods described herein, a user can choose to operate under carbon dioxide neutral conditions so that excess carbon dioxide does not have to be flared or vented to the atmosphere.

[0032] 1A and 1B are block diagrams of an oxidative dehydrogenation system 100 for the oxidative dehydrogenation of light hydrocarbons, according to an embodiment. The oxidant typically used in the process is air 102, although oxygen, typically mixed with a diluent, can also be used. Air 102 enters an air separation unit (ASU) 104. In the ASU 104, oxygen 106 is separated from other gases, such as nitrogen and carbon dioxide, among others. The oxygen 106 may then be mixed with a diluent in, for example, a steam dilution system 108.

[0033] To avoid process upsets, many embodiments use mixtures of one or more alkanes and oxygen with ratios of the one or more alkanes to oxygen outside the flammability envelope. In some embodiments, the ratio of alkane to oxygen may be outside the upper limit of the flammability envelope. In these embodiments, the percentage of oxygen in the mixture may be greater than zero but less than 30% by weight, in some cases less than 25% by weight, or in other cases less than 20% by weight.

[0034] In embodiments with a higher percentage of oxygen, the percentage of alkane can be adjusted to keep the mixture outside the flammability envelope. One skilled in the art can determine the appropriate ratio level, but in many cases the percentage of alkane is greater than zero and less than about 40% by volume. As a non-limiting example, if the mixed gas before the ODH contains 20% by volume of oxygen and 40% by volume of alkanes, the remainder can be made up with an inert diluent. Non-limiting examples of inert diluents useful in this embodiment include, but are not limited to, one or more of steam, nitrogen, carbon dioxide, and the like. In some embodiments, the inert diluent should be present in a gaseous state at the conditions in the reactor and should not increase the flammability of the hydrocarbons added to the reactor, the characteristics of which will be understood by one skilled in the art when determining which inert diluent to use. The inert diluent can be added to the alkane-containing gas or oxygen-containing gas before entering the ODH reactor, or can be added directly to the ODH reactor.

[0035] While many different hydrocarbons can be used, in the oxidative dehydrogenation process, ethane is generally fed to the reactor along with oxygen. In some embodiments, the volumetric feed ratio of oxygen to ethane (O2 / C2H6) fed to one or more ODH reactors can be at least about 0.3, in some cases at least about 0.4, and in other cases at least about 0.5, and can be up to about 1, in some cases up to about 0.9, in other cases up to about 0.8, in some cases up to about 0.7, and in other cases up to about 0.6. The volumetric feed ratio of oxygen to ethane can be any value or range between any values ​​recited above.

[0036] In some embodiments, mixtures that fall within the flammable envelope may be used, for example, when the mixture exists under conditions that prevent the propagation of an explosive event. In these non-limiting examples, the flammable mixture is generated in a medium where ignition is quickly extinguished. As a further non-limiting example, a user may design a reactor where oxygen and one or more alkanes are mixed at a point surrounded by flame suppression material. Any ignition is extinguished by the surrounding material. Flame suppression materials include, but are not limited to, metallic or ceramic components such as stainless steel walls and ceramic supports. In some embodiments, oxygen and alkanes may be mixed at a low temperature such that an ignition event would not lead to an explosion, and then introduced into the reactor before the temperature increases. Flammable conditions do not exist until the mixture is surrounded by flame suppression material inside the reactor.

[0037] The amount of steam added to the ODH process in the steam dilution system 108 affects the extent to which carbon dioxide acts as an oxidant. In some embodiments, steam may be added directly to the ODH reactor 110, or steam may be added to an individual reactant (lower alkane, oxygen, or inert diluent) or combination thereof and then introduced into the ODH reactor 110 with one or more reactants. Alternatively, steam may be added indirectly as water mixed with either the lower alkane, oxygen, or inert diluent, or combination thereof, and the resulting mixture may be preheated before entering the reactor. If steam is added indirectly as water, a heater 112 is used to increase the temperature so that the water is completely converted to steam before entering the reactor.

[0038] Increasing the amount of steam added to the ODH reactor 110 increases the extent to which carbon dioxide acts as an oxidant. Reducing the amount of steam added to the ODH reactor 110 decreases the extent to which carbon dioxide acts as an oxidant. In some embodiments, a user monitors the carbon dioxide output and compares it to a predetermined target carbon dioxide output. If the carbon dioxide output is above the target, the user can increase the amount of steam added to the ODH process. If the carbon dioxide output falls below the target, the user can decrease the amount of steam added to the ODH process, if steam is being added. Setting the target carbon dioxide output level depends on the user's requirements. In some embodiments, increasing the amount of steam added has the additional effect of increasing the amount of acetic acid and other by-products produced during the process. Higher steam levels produce more acetic acid from the ODH, so reducing the steam level reduces the amount produced. Conversely, higher steam levels consume more carbon dioxide.

[0039] In some embodiments, the amount of steam added to the ODH reactor 110 can be up to about 50% by volume, in some circumstances up to about 40% by volume, in some circumstances up to about 35% by volume, in other cases up to about 30% by volume, in some cases up to about 25% by volume, and can be zero, in some circumstances at least 0.5% by volume, in other cases at least 1% by volume, in other cases at least 5% by volume, in some cases at least 10% by volume, and in other cases at least 15% by volume of the stream entering the ODH reactor 110. The amount of steam in the stream entering the ODH reactor 110 can be any value or range between any of the values ​​recited above. As used herein, the ODH reactor 110 can include a single reactor or multiple reactors.

[0040] In some embodiments, when more than one ODH reactor is used, the user may choose to control the carbon dioxide emissions in only one reactor, or in fewer than the entire set of reactors. For example, the user may maximize the carbon dioxide emissions in an upstream reactor, allowing higher levels of carbon dioxide to become part of the inert diluent for the subsequent reactor. In that case, maximizing the carbon dioxide emissions upstream may minimize the amount of inert diluent that needs to be added to the stream before the next reactor.

[0041] It is not essential to add steam to the ODH process, as the addition of steam is one of many options for the inert diluent. In processes without added steam, the carbon dioxide emissions are maximized under the conditions used for the input of ethane, oxygen, and inert diluent. Reduction of carbon dioxide emissions can be achieved by adding steam to the reaction until the carbon dioxide emissions are reduced to a desired level. In embodiments where the oxidative dehydrogenation or conditions for the oxidative dehydrogenation do not include the addition of steam and the carbon dioxide emissions are higher than the desired carbon dioxide target level, steam can be introduced to the reactor, the carbon dioxide emissions monitored, and the amount of steam increased until the carbon dioxide emissions are reduced to the target level, while keeping constant the relative amounts of the main reactants and inert diluent (lower alkane, oxygen, and inert diluent) added to the reactor.

[0042] In some embodiments, a carbon dioxide neutral process can be achieved by increasing the steam addition so that the carbon dioxide produced in the oxidative dehydrogenation process is used as the oxidant and there is no net production of carbon dioxide. Conversely, if the user desires a net carbon dioxide emission, the amount of steam added to the process can be reduced or eliminated to maximize the production of carbon dioxide. Increasing the carbon dioxide level can reduce oxygen consumption as carbon dioxide competes as an oxidant. One skilled in the art will appreciate that using steam to increase the extent to which carbon dioxide acts as an oxidant can affect oxygen consumption. The implication is that the user can optimize the reaction conditions with a lower oxygen contribution and keep the mixture within the flammability limits.

[0043] From the heater 112, the feed is introduced into the ODH reactor 110. The ODH reactor 110 can be any of the known reactor types applicable to selective oxidation processes such as ODH of alkanes. In some embodiments, the ODH reactor 110 is a conventional fixed bed reactor. In a typical fixed bed reactor, reactants are introduced at one end of the reactor and flow through an immobilized catalyst while products are formed. The products exit the ODH reactor 110 at the end opposite to where the feed was introduced. The design of a fixed bed reactor suitable for the methods disclosed herein can follow known techniques for this type of reactor. Those skilled in the art will know what features are required in terms of shape and dimensions, reactant input, product output, temperature and pressure control, means of immobilizing the catalyst, etc.

[0044] In some embodiments, inert non-catalytic heat dissipating particles can be used in one or more ODH reactors. In various embodiments, the heat dissipating particles are present in the bed and include one or more non-catalytic inert particulates. The non-catalytic inert particulates have a melting point at least 30° C., in some embodiments at least 250° C., and in further embodiments at least 500° C., above the upper temperature control limit of the reaction; have a particle size in the range of 0.5-75 mm, in some embodiments 0.5-15 mm, in further embodiments 0.5-8 mm, and in further embodiments 0.5-5 mm; and have a thermal conductivity of greater than 30 W / mK (Watts per meter Kelvin) within the reaction temperature control limit. In some embodiments, the particulates are metal alloys and compounds that have a thermal conductivity of greater than 50 W / mK (Watts per meter Kelvin) within the reaction temperature control limit. In some embodiments, the particulates are minerals or metal oxides. Non-limiting examples of suitable metals that can be used in these embodiments include, but are not limited to, silver, copper, gold, aluminum, steel, stainless steel, molybdenum, tungsten, and silica sand.

[0045] The heat dissipating particles can have a particle size of about 1 mm to about 15 mm. In some embodiments, the particle size can be about 1 mm to about 8 mm. The heat dissipating particles can be added to the fixed bed in an amount of 5 to 95 wt%, in some embodiments 30 to 70 wt%, and in other embodiments 45 to 60 wt%, based on the total weight of the fixed bed. The particles are potentially used to improve the uniformity of cooling and reduce hot spots within the fixed bed by directly transferring heat to the walls of the reactor. As described herein, in embodiments, the ODH reactor 110 may be cooled by generating high pressure steam 114, for example, in a jacket around the ODH reactor 110 or in a coil within the ODH reactor 110.

[0046] Additional embodiments include the use of a fluidized bed reactor, where the catalyst bed can be supported by a porous structure, or distribution plate, located near the bottom end of the reactor, and the reactants flow at a velocity sufficient to fluidize the bed (e.g., the catalyst rises, becomes fluidized, and begins to swirl). The reactants are converted to products upon contact with the fluidized catalyst, and the reactants are then removed from the top of the reactor. Design considerations that one skilled in the art can modify and optimize include, but are not limited to, reactor geometry, distribution plate shape and size, inlet temperature, outlet temperature, and reactor temperature and pressure controls.

[0047] Some embodiments include the use of a combination of both fixed bed and fluidized bed reactors, each reactor containing the same or different ODH catalyst. Multiple reactors can be arranged in series or parallel configurations, the design of which is within the knowledge of one of ordinary skill in the art.

[0048] In some embodiments, the stream exiting the one or more ODH reactors can be treated to remove or separate water and water-soluble hydrocarbons from the stream exiting the one or more ODH reactors, hi some embodiments, this stream is fed to a second reactor.

[0049] In some embodiments, the stream exiting the ODH reactor 110 is directed to a quench tower 118 where it is cooled and condensed. This facilitates the removal of oxygenates, such as water 120 and acetic acid 122, via a bottom outlet that feeds an acetic acid separator 124. The acetic acid separator 124 separates the acetic acid stream 122 from the water 120 as well as a gas stream that is returned to an acetic acid scrubber 126. The water 120 may be treated in a biooxidation unit 128 to remove residual carbon compounds, such as trace amounts of acetic acid, among other things. From the biooxidation unit 128, the water 120 may be fed as a make-up stream to a cooling tower 130.

[0050] The remaining gas from quench tower 118, along with the separated gas from acetic acid separator 124, is fed to acetic acid scrubber 126. Acetic acid scrubber 126 can remove trace amounts of acetic acid and other carbon compounds from these gas streams by oxidation or adsorption.

[0051] Stream 132, containing unconverted lower alkane (such as ethane), the corresponding alkene (such as ethylene), unreacted oxygen, carbon dioxide, carbon monoxide, and optionally acetylene and an inert diluent, exits acetic acid scrubber 126 and is fed to an oxygen removal system 134 (FIG. 1B), or to a second reactor (as described with respect to FIGS. 2 and 3). In some embodiments, a portion 133 of stream 132 is recycled to the reaction, for example, by being returned to steam dilution system 108 for mixing with the feed stream to reactor 110.

[0052] The oxygenates removed via the quench tower 118 and / or acetic acid scrubber 126 can include carboxylic acids (e.g., acetic acid), aldehydes (e.g., acetaldehyde), and ketones (e.g., acetone). The amount of oxygenates remaining in the stream 132 exiting the scrubber and fed to the oxygen removal system 134 is often zero, e.g., below the detection limit of an analytical test method typically used to detect such compounds. If oxygenates are detected, they may be present at levels up to about one part per million by volume (ppmv), in some cases up to about 5 ppmv, in other cases less than about 10 ppmv, in some cases up to about 50 ppmv, in other cases up to about 100 ppmv, and may be present up to about 2% by volume, in some cases up to about 1% by volume, and in other cases up to about 1,000 ppmv. The amount of oxygenates or acetic acid in the stream exiting the scrubber and fed to the oxygen removal system 134 can be any value or range between any values ​​recited above.

[0053] In the oxygen removal system 134, a high temperature membrane may be used to remove oxygen from stream 132 exiting the acetic acid scrubber 126, as described herein. The high temperature membrane may be heated by burning access hydrocarbons in stream 132, or by burning fuel added to the oxygen removal system 134, or both. Stream 101 exiting the acetic acid scrubber 126 may be recycled to the steam dilution system 108.

[0054] The stream 132 from the oxygen removal system may be compressed, for example, in a first compressor system 136. The first compressor system 136 may include a single compressor or a series of compressors that successively increase the pressure of the stream 132. The compressed stream may then be fed to an amine scrubber 138 to remove CO2 140 from the compressed stream, as described in further detail herein. From the amine scrubber 138, the compressed stream may be fed to a caustic scrubber 142, which further reduces the concentration of CO2 in the compressed gas stream and sends the CO2 into a rich caustic stream 144. The rich caustic stream 144 may then be processed to form a lean caustic stream, which may be returned to the caustic scrubber 142.

[0055] The purified gas stream from the caustic scrubber 142 may contain unconverted lower alkanes (such as ethane) and corresponding alkenes (such as ethylene), as well as excess inert diluent (such as nitrogen). The purified gas stream may be compressed in a second compressor system 146. The second compressor system 146 may include a single compressor or a series of compressors that successively increase the pressure of the purified gas. The compressed purified gas may then be sent to a dryer 148 to remove excess water vapor from the amine scrubber 138 and the caustic scrubber 142. The dryer 148 may include molecular sieves to absorb water or may include a series of heat exchangers and coolers to physically condense the water, or may include both.

[0056] The dried stream is then sent to a cooler 150, which may include a series of heat exchangers, such as propane-cooled heat exchangers, compressed nitrogen-cooled heat exchangers, and heat exchangers cooled by fluids from other parts of the process. The cooler 150 may be integrated with or feed into a depropanizer (C3R) 152, a deethanizer (C2R) 154, or both.

[0057] Returning to FIG. 1A, the cooled gas stream is fed to a demethanizer 156. From the demethanizer 156, an off-gas stream 158 is sent to waste or a downstream process. The off-gas stream 158 includes the remainder of the inert diluent and the methane removed from the cooled gas stream. Additionally, the demethanizer 156 returns a portion of the C2 compounds, such as ethylene and ethane, to the process upstream of the first compressor system 136. The C2 stream from the demethanizer 156 is fed to a C2 splitter 160.

[0058] A C2 splitter 160 splits the C2 stream into an ethylene product stream 162 and an ethane feed stream 164. The ethane feed stream 164 is vaporized in heat exchanger 166 to form an ethane gas feed stream. Ethane feed 168 from a separate ethane source may be vaporized in heat exchanger 170 and mixed into the ethane gas feed stream.

[0059] The ethane gas feed stream then passes through high temperature heat exchanger 172 and is superheated. The superheated ethane gas feed stream is then provided to steam dilution system 108 for use in the process. The core reaction process, including oxygenate separation, amine wash, and caustic wash, is further described below with reference to Figures 2 and 3.

[0060] FIG. 2 is a diagram of a chemical complex 200 according to some embodiments. In the following description, identical parts are labeled with the same reference numerals. In some embodiments, the chemical complex, one embodiment of which is shown in schematic form in FIG. 2, includes, in a coordinated arrangement, an ODH reactor 202, a quench tower and / or acetic acid scrubber 204, a second reactor 206 (as described herein), an amine scrubber 208, a dryer 210, a distillation tower 212, and an oxygen separation module 214. The ODH reactor 202 includes an ODH catalyst capable of catalyzing an oxidative dehydrogenation reaction of an alkane introduced via an alkane line 218 in the presence of oxygen, which may be introduced via an oxygen line 216. The second reactor 206 is shown immediately after the quench tower or acetic acid scrubber 204, but can be located further downstream. In many cases, the process configuration is more energy efficient if the second reactor 206 is located after the input stream is compressed.

[0061] The ODH reaction may also occur in the presence of an inert diluent, such as carbon dioxide, nitrogen, steam, etc., that is added to ensure that the mixture of oxygen and hydrocarbons is outside of flammability limits. As described herein, the inert diluent may or may not participate in the ODH reaction (e.g., carbon dioxide or steam) or may not participate (e.g., nitrogen). It is within the knowledge of one of ordinary skill in the art to determine whether a mixture is outside of flammability limits at a given temperature and pressure. The ODH reaction occurring in the ODH reactor 202 may also produce various other products, including carbon dioxide, carbon monoxide, oxygenates, and water, depending on the catalyst and the prevailing conditions in the ODH reactor 202. These products, along with unreacted alkanes, corresponding alkenes, residual oxygen, carbon monoxide, and the inert diluent (if added), exit the ODH reactor 202 via the ODH reactor product line 220.

[0062] The ODH reactor product line 220 is directed to a quench tower or acetic acid scrubber 204 which quenches the product from the ODH reactor product line 220 and facilitates removal of oxygenates and water via a quench tower bottom outlet 222. The unconverted lower alkanes, corresponding alkenes, unreacted oxygen, carbon dioxide, carbon monoxide, and inert diluent added to the quench tower or acetic acid scrubber 204 exit through a quench tower overhead line 224 and are sent to the second reactor 206.

[0063] The second reactor 206 contains a Group 11 metal with optional promoter and optional support as described above, which reacts unreacted oxygen with carbon monoxide to form carbon dioxide or, optionally, reacts acetylene with carbon monoxide to reduce or eliminate carbon monoxide. In the second reactor 206, most or all of the unreacted oxygen and acetylene are consumed. All or a portion of the carbon dioxide in the second reactor 206 can be recycled back to the ODH reactor 202 via recycle lines 226 and 227 to act as an oxidant as described above. The remaining unconverted lower alkane, the corresponding alkene, unreacted oxygen (if present), all or a portion of the carbon dioxide, carbon monoxide (if present), and inert diluent are conveyed to the amine wash column 208 via line 228.

[0064] Carbon dioxide present in line 228 is separated by the amine scrubber 208 and captured via carbon dioxide bottom outlet 230 and may be sold or recycled back to the ODH reactor 202 as described above. Components other than carbon dioxide introduced into the amine scrubber 208 via line 228 exit the amine scrubber 208 through amine scrubber overhead line 232 and pass through dryer 210 before being sent to distillation column 212 via line 234. In distillation column 212, the C2 / C 2+ Hydrocarbons are separated and C2 / C 2+The remaining fraction, consisting primarily of C1 hydrocarbons (including residual inert diluent and carbon monoxide, if present), exits distillation column 212 via overhead stream 238 and is sent to oxygen separation module 214.

[0065] Oxygen separation module 214 includes a sealed vessel with a retentate side 240 and a permeate side 242 separated by an oxygen transport membrane 244. Overhead stream 238 can be directed to either retentate side 240 or permeate side 242. Optionally, flow control means can be included to allow for varying levels of inflow to both sides, as described herein. An operator can then select which portion of the flow from overhead stream 238 enters retentate side 240 and which portion enters permeate side 242. Depending on conditions, an operator can switch between either the retentate or permeate side, allow equal amounts to both sides, or allow biased amounts to either side. Oxygen separation module 214 also includes an air inlet 246 for introducing atmospheric air or other oxygen-containing gas into retentate side 240. Combustion of products introduced into retentate side 240 by the introduction of oxygen can contribute to raising the temperature of oxygen transport membrane 244 to at least about 850° C., allowing oxygen to pass from retentate side 240 to permeate side 242. Atmospheric components or other oxygen-containing gases other than oxygen cannot pass from retentate side 240 to permeate side 242 and can only exit oxygen separation module 214 via exhaust vent 248 .

[0066] The passage of oxygen from retentate side 240 to permeate side 242 effects the separation of oxygen from air or other oxygen-containing gases introduced into retentate side 240. As a result, an oxygen-enriched gas is produced in permeate side 242, which is sent to ODH reactor 202 via oxygen-enriched bottom line 227 (as shown in FIG. 1 ), either directly or in combination with oxygen line 216. When overhead stream 238 is sent to retentate side 240, the purity of oxygen in oxygen-enriched bottom line 220 may approach 99% by volume. Conversely, when overhead stream 238 is sent to permeate side 242, the purity of oxygen in oxygen-enriched bottom line 220 will be lower, with an upper limit in the range of 80% to 90% by volume oxygen, with the remainder in the form of carbon dioxide, water, and residual inert diluents, all of which may be entrained with the enriched oxygen to ODH reactor 202 without affecting the ODH reactions envisioned by the present disclosure. Water and carbon dioxide can be removed by quench tower 204 and amine scrubber 208, respectively. In some embodiments of the present disclosure, some or all of the carbon dioxide can be captured for sale as opposed to incineration, which causes greenhouse gas emissions. In other embodiments, the carbon dioxide captured in the amine scrubber can be recycled to the ODH reactor 202 if the carbon dioxide is used in an ODH process.

[0067] Oxygen transport membrane 244 is temperature dependent and only allows oxygen transport when the temperature reaches at least about 850° C. In some embodiments, the components in overhead stream 238 are not themselves capable of raising the temperature of oxygen transport membrane 244 to the required level upon combustion in the presence of oxygen. In this embodiment, the chemical complex of the present disclosure also includes a fuel augmentation line 250 upstream of oxygen separation module 214 where a combustible fuel, such as, by way of non-limiting example, methane, can be added to supplement the combustible products from overhead stream 238.

[0068] In some embodiments, a concern in the ODH process is the mixing of the hydrocarbon with oxygen. Under certain conditions, the mixture may become unstable and cause an explosion. A mixer can be used to mix the hydrocarbon-containing gas with the oxygen-containing gas in an open flooded mixing vessel. This mixing ensures that pockets of unstable composition are surrounded by non-flammable liquid, so that any ignition event is quickly extinguished. If the addition of gas to the ODH reaction is controlled so that, under the given conditions of temperature and pressure, the homogeneous mixture is outside the flammability envelope, a safe homogeneous mixture of hydrocarbon and oxygen is obtained.

[0069] In some embodiments, upstream of the ODH reactor 202 is a flooded gas mixer 302 (FIG. 3). In this example, the oxygen line 216 and the alkane line 218 are fed directly into the flooded gas mixer 302. A homogeneous mixture comprising hydrocarbons and oxygen, and optionally an inert diluent, can be introduced from the flooded gas mixer 302 to the ODH reactor 202 via mixing line 304 (FIG. 3). The oxygen-enriched bottom line 227 can be fed directly to the flooded gas mixer 302 or can be fed to the flooded gas mixer 302 in combination with the oxygen line 216.

[0070] The temperature of the contents in product line 220 in a typical ODH process can reach approximately 450° C. As mentioned above, it may be desirable to reduce the temperature of the stream before introduction to the quench tower or acetic acid scrubber 204. In that case, the present disclosure contemplates the use of heat exchangers immediately downstream of each ODH reactor 202 and immediately upstream of the acetic acid scrubber 204. The use of heat exchangers for such temperature reduction is well known in the art.

[0071] Figure 3 is a diagram of a chemical complex 300 according to some embodiments. As discussed above with reference to Figure 2, in the ODH process configuration shown in Figure 3, the second reactor 206 is shown immediately after the quench tower or acetic acid scrubber 204, but can be located further downstream. In many cases, the process configuration will be more energy efficient if the second reactor 206 is located after the input stream is compressed.

[0072] In some embodiments, the olefins produced using one or more ODH reactors or any of the processes or complexes described herein can be used to produce a variety of olefin derivatives, including, but not limited to, polyethylene, polypropylene, ethylene oxide, propylene oxide, polyethylene oxide, polypropylene oxide, vinyl acetate, vinyl chloride, acrylic esters (e.g., methyl methacrylate), thermoplastic elastomers, thermoplastic olefins, and blends and combinations thereof.

[0073] In some embodiments, ethylene and optionally α-olefins are produced in one or more ODH reactors or any of the processes or complexes described herein and used to produce polyethylene. The polyethylenes produced from the ethylene and optionally α-olefins described herein can include homopolymers of ethylene, copolymers of ethylene and α-olefins, resulting in HDPE, MDPE, LDPE, LLDPE, and VLDPE.

[0074] The polyethylenes produced using ethylene and any α-olefins described herein can be produced using any suitable polymerization process and equipment. Suitable ethylene polymerization processes include, but are not limited to, gas phase polyethylene processes, high pressure polyethylene processes, low pressure polyethylene processes, solution polyethylene processes, slurry polyethylene processes, and suitable combinations of the above arranged in parallel or series.

[0075] The present disclosure also contemplates the use of various tools commonly used in chemical reactors, including flow meters, compressors, valves, and sensors for measuring parameters such as temperature, pressure, and flow rate. One of ordinary skill in the art is expected to include these components as deemed necessary for safe operation. EXAMPLES

[0076] <General Procedure>

[0077] <Reagents> Reagents purchased from manufacturers were used as received without further purification. All reagents except niobium(V) oxide hydrate and ammonium hydroxide were purchased from Sigma Aldrich. Ammonium molybdate ((NH4)6Mo7O 24 Vanadium(IV) oxide sulfate hydrate (VOSO4·3.41H2O), telluric acid (Te(OH)6), oxalic acid, and sulfuric acid 95-98% were purchased from Sigma Aldrich. The provided certificates of analysis were used to establish the hydrate content of the different batches. Niobium(V) oxide hydrate (Nb2O5·xH2O) was purchased from Companhia Brasileira de Metalurgia e Mineracao (CBMM) as product Niobia HY-340, containing 20% ​​water by weight. Ammonium hydroxide 28-30% was purchased from Anachemia, a VWR company. Distilled water was prepared in-house using a Corning Mega Pure 12A System ACS as the distillation apparatus.

[0078] [Table 1]

[0079] <mru> FIG. 4 is a schematic diagram of a microreactor unit (MRU) 400 as described in the Examples. The catalysts and catalyst materials described herein were tested in the MRU 400 for their ability to participate in the oxidative dehydrogenation reaction of ethane. The MRU 400 is comprised of a fixed-bed tubular reactor 402 surrounded by a two-zone electric heater 404. The fixed-bed tubular reactor 402 is a SWAGELOK® 316L stainless steel tube with an outer diameter of 0.5 inches (about 1.27 cm), an inner diameter of 0.4 inches (about 1 cm), and a length of 14.96 inches (about 38 cm). Two main feed gas lines are connected to the reactor 402. One line 406 is dedicated to bulk nitrogen purge gas, while the other line 408 is connected to a dual solenoid valve that allows switching from the ODH process feed gas (a gas mixture with an ethane / oxygen / nitrogen molar ratio of about 36 / 18 / 46) to compressed air when regenerating the catalyst bed.

[0080] A six-point WIKA Instruments Ltd. K-type thermocouple 410 (having an outer diameter of 0.125 inches) was inserted into the reactor 402 and used to measure and control the temperature in the catalyst bed 412. Details of the thermocouple 410 are shown in Figure 5. A room temperature glass sealed condenser was placed after the reactor to collect the water / acid condensate. The gas product stream was either vented or sent via a sampling loop to a gas chromatograph (Agilent 6890N gas chromatograph, using Chrom Perfect-Analysis, version 6.1.10 for data evaluation).

[0081] To prepare catalysts and catalyst materials for testing in the MRU400, the catalyst or catalyst material was loaded into a 1 inch round die and pressed with a compression force of 8 tons for a residence time of 10 seconds to 15 seconds. The pressed catalyst or catalyst material was then crushed into small pieces using a mortar and pestle. The crushed catalyst or catalyst material was sieved and particles of 425 μm to 1000 μm in size were collected and loaded for testing in the MRU.

[0082] For safety reasons, the unit is programmed to prevent air from mixing with the feed gas. This is accomplished by safety interlocks and a mandatory 15 minute nitrogen purge of the reactor when switching between feed gas supplied through line 408 and air 414 supplied through line 406. The gas flow rates are controlled by mass flow controllers. Catalyst is loaded into the middle zone of the reactor 402 forming the catalyst bed 412. The remainder of the reactor 402 (below and above the catalyst bed 416) is filled with 100% silica sand and the load is secured to the top and bottom of the reactor 402 with glass wool. A glass sealed condenser 418 is placed after the reactor 402 at room temperature to collect the water / acid and the gas product can flow to either the vent 420 or the sampling loop / vent 422 by a three-way solenoid valve.

[0083] The catalyst bed 412 disposed within the reactor tube may include a catalyst or catalytic material and a packing material. In the MRU experiments described herein, the catalyst bed 412 was prepared by physically mixing 1.96 g of catalyst with quartz sand such that the total volume of the catalyst bed 412 was approximately 3 mL. The quartz sand acts as a packing material or heat sink. As described herein, packing material refers to a material that does not participate in the oxidative dehydrogenation of ethane or has no other catalytic activity, such as non-selective oxidation, under the MRU test conditions. The ratio of catalyst or catalytic material to packing material is 1:1 (by volume). The catalyst bed 412 was loaded into the middle zone of the reactor (e.g., located between thermocouple measurement points 2 and 5), and the remaining volume of the reactor was packed with quartz sand. The load was then secured to the top and bottom of the reactor with glass wool.

[0084] 5 is a diagram of the MRU thermocouples and shows the locations of the six thermocouple measurement points. As described herein, the catalyst bed is loaded into the reactor such that it is located between thermocouple measurement points 2 and 5.

[0085] In the MRU test, a premixed (pre-mixed) feed gas was fed to the reactor. The premixed feed gas entering the reactor was 35 mol% ethane, 17.5 mol% oxygen, and 47.5 mol% nitrogen. Furthermore, the flow rate of the premixed feed gas was adjusted by a calibrated mass flow controller and was maintained at 2.90 h based on the weight of catalyst in the catalyst bed. -1 A constant weight hourly space velocity (WHSV) of 74.6 standard cubic centimeters per minute (sccm) was obtained. The flow rate of the feed gas was controlled via a mass flow controller at a set point of 74.6 standard cubic centimeters per minute (sccm).

[0086] The 35% conversion temperature (also referred to herein as the 35 mole % ethane conversion temperature or 35% conversion temperature) is a temperature at which the weight hourly space velocity (WHSV) is 2.90 h -1 , and Gas Hourly Space Velocity (GHSV) of approximately 3,000h -1 where WHSV is based on the amount of catalyst or the amount of catalyst used to prepare the catalyst material, where WHSV is defined as the mass flow rate of the feed gas to the reactor divided by the weight of catalyst in the catalyst bed, and GHSV is defined as the volumetric flow rate of the reactor feed gas divided by the volume of the catalyst bed.

[0087] Typically, the inlet pressure ranged from about 1 pound per square inch gauge (psig) to about 2.5 psig, and the outlet pressure ranged from about 0 psig to about 0.5 psig. The gas feed leaving the catalyst bed can be analyzed by gas chromatography to determine the proportions of various hydrocarbons (e.g., ethane and ethylene), and optionally other gases such as O2, CO2, and CO.

[0088] The gases exiting the reactor were analyzed by gas chromatography (Agilent 6890N gas chromatograph, Chrom Perfect-Analysis, version 6.1.10, used for data evaluation) to determine the proportions of different hydrocarbons (e.g., ethane and ethylene) and, optionally, other gases such as O2, CO2, CO, acetylene, etc.

[0089] The 35% conversion temperature of the catalyst or catalytic material was determined as follows. The feed gas conversion was calculated as the change in ethane mass flow rate in the product relative to the feed ethane mass flow rate using the following equation: TIFF2024509101000003.tif25150

[0090] In the above equation, C is the percentage of the feed gas converted from ethane to another product (i.e., ethane conversion), and X is the molar concentration of the corresponding compound in the gaseous effluent exiting the reactor at the corresponding temperature. The ethane conversion was then plotted as a function of temperature to obtain a linear algebraic equation. The linear equation for ethane conversion was solved to determine the temperature at which ethane conversion was 35%, i.e., the 35% conversion temperature.

[0091] Additionally, the gases exiting the reactor were analyzed by gas chromatography to determine the ethylene selectivity of the catalyst or catalyst material (i.e., the proportion of ethane on a molar basis that forms ethylene). The ethylene selectivity was determined using the following equation: TIFF2024509101000004.tif25150

[0092] In the above formula, S エチレン is the selectivity to ethylene, and X is the molar concentration of the corresponding compound in the gaseous effluent leaving the reactor at the corresponding temperature. The selectivity to ethylene was measured at the 35% conversion temperature unless otherwise stated. Thus, after determining the 35% conversion temperature, X at the 35% conversion temperature was calculated. エチレン , X CO2 , X CO The above equation for selectivity was solved using the corresponding values ​​of

[0093] <icp-ms> Inductively Coupled Plasma Mass Spectrometry (ICP-MS) is an analytical technique used to measure the elemental composition of catalysts or catalytic materials, with sufficient sensitivity to detect elements in the ppb concentration range. ICP-MS analysis was performed on an Agilent 7700X ICP-MS system. Liquid samples were aerosolized through a nebulizer and spray chamber and introduced into the ICP. An argon plasma dried the aerosol and dissociated the sample molecules into atomic ions. The ions were directed to the MS detector, separated based on their mass-to-charge ratio, and measured by the detector, generating a signal proportional to the concentration of the ions. Quantitative determination of the atomic concentrations in the original samples was determined using external standard calibration. A calibration curve was constructed after subtraction of the reagent blank. In this analysis, atomic concentrations were expressed in units of ng / mg (ppm by weight) or μg / g (ppm by weight).

[0094] A general ICP-MS procedure for catalysts containing molybdenum, vanadium, niobium, and tellurium.

[0095] Samples were prepared by placing approximately 10-20 mg of catalyst material and 3.5-4.0 g of oxalic acid in a vial. 15-20 mL of distilled water was then added to create a suspension. The suspension was heated in an oil bath at 90 °C with vigorous mixing. Dissolution of the catalyst typically took 24-72 hours to produce a homogenous blue solution. After dissolution was complete, the resulting blue solution was diluted to a final volume of 60-80 mL. The diluted solution was then further diluted 10-100 times using 5% nitric acid and analyzed by ICP-MS.

[0096] In a typical ICP-MS multi-element scan, the instrument parameters are optimized to scan trace (ppb) levels of over 50 elements. However, Nb is not included in the over 50 elements in this multi-element scan, and it is not calibrated for higher concentrations (e.g., concentrations exceeding about 10 wt%). Therefore, when scanning the four elements present in the catalyst sample, a calibration standard sample with a higher concentration was used, and since the target elements were detected at the percent level, the sensitivity of the instrument decreased. This was done by preparing calibration standard samples for each of the four elements. These calibration standard samples were prepared at percent levels (high ppm concentrations) of Mo, V, Nb, and Te. The ICP-MS program was developed so that only the four elements could be detected with high precision. Therefore, the detector was calibrated for the high ppm concentrations of the four target elements, and the over 50 elements that are normally calibrated for ppm-level concentrations were excluded.

[0097] <CHH+S Analysis> CHN+S analysis was performed on the selected samples using a LECO CHN628 series measuring instrument equipped with a sulfur add-on module. The combustion of the samples and the generated gas analysis technology were used to determine the carbon, hydrogen, nitrogen, and sulfur contents. The pre-weighed and encapsulated samples were placed in the loader of the measuring instrument, where the samples were transferred to the purge chamber of the instrument directly above the furnace, and the atmospheric gas was removed during the transfer process. Then, the samples were introduced into a primary combustion furnace containing only pure oxygen. This caused rapid and complete oxidation. The carbon, hydrogen, nitrogen, and sulfur present in the samples were oxidized to form CO2, H2O, NO x 、SO x gases, which were swept through a secondary furnace by an oxygen carrier, and further oxidation and particulate removal were performed.

[0098] Next, the mixed gas was collected in a container called a ballast for equilibration. The homogenized gas from the ballast was 10 cm 2 The NO is swept through an aliquot loop into the detector using ultra-high purity helium carrier gas. Separately optimized non-dispersive infrared (NDIR) cells are used for the detection of CO2, SO2, and H2O. x Gas is NO x The gas passes through a copper-filled reduction tube to reduce it to N2, and excess oxygen is removed from the combustion process. The removed gas then passes through a scrubber to remove CO2 and H2O, and is sent to a thermal conductivity cell (TC) used to detect N2. Before each set of samples, the instrument is calibrated using certified standards.

[0099] <ftir> Fourier transform infrared spectroscopy (FTIR) is a technique used to obtain infrared spectra (IR) of solid or liquid samples by irradiating the sample with monochromatic light and measuring the absorbance over a range of wavelengths. The FTIR technique can be used as a fingerprinting technique to overlay the IR spectrum of an unknown sample with that of a known sample, or it can be used to identify characteristic absorptions that represent specific types of molecular bonds (e.g., C=O, OH, NH, CH, CO, SO, S=O, etc.). Solid samples for FTIR scans were prepared by the pressed KBr pellet method. Liquid samples for FTIR scans were prepared by placing a small amount of liquid sample on top of a first KBr cell and then pressing a second KBr cell on top of the first. The instrument in situ was a Bruker Tensor27 FTIR spectrophotometer using a laser with an operating wavelength of 633 nm.

[0100] FTIR is a useful method to screen LEEP catalysts before calcination because sulfate anions have distinct emission frequencies in the infrared spectrum and can be used to qualitatively screen whether the catalyst contains residual sulfate anions (wt%). Details of the SO / S=O emission peaks are provided in the Results section.

[0101] <Yield calculation> Theoretical yield calculations were based on the moles of metal salts used in the preparation. The theoretical moles of final product were predicted by assuming that molybdenum, vanadium, tellurium, and niobium reached their highest oxidation states in the product after the hydrothermal reaction. Thus, molybdenum, vanadium, niobium, and tellurium formed MoO3, V2O5, Nb2O5, and TeO3, respectively. The moles of starting material were multiplied by the respective molar equivalents of each oxidized species. This mole was then multiplied by the predicted theoretical weight of the fully oxidized final product to obtain the final theoretical weight of the catalyst.

[0102] For example, the following weights and moles of salts were used: (NH4)6Mo7O 24 4H2O = 4865.0 g; 3.94 mol; VOSO4·3.41H2O = 4023.5 g; 18.01 mol; Nb2O5·3.69H2O = 656.3 g; 1.98 mol; and Te(OH)6 = 1054.6g; 4.59mol Therefore, the theoretical yields, weights and moles of the corresponding oxides are: MoO3 = 4628.4 g; 32.16 mol; V2O5 = 1638.0 g; 9.01 mol; Nb2O5 = 525.1 g; 1.98 mol; TeO3 = 806.6 g; 4.59 mol; and Total theoretical mass = 7598.07g. For example, if the mass of the recovered product is 6300 g, the yield of the preparation is about 83%. The percent yield was determined by dividing the actual measured yield by the theoretical yield and multiplying by 100.

[0103] <Synthesis of catalyst compositions 1.1 to 1.8 (uncalcined samples)> General synthesis procedure for uncalcined catalyst compositions 1.1-1.7 10 L of distilled water was added to the vessel and heated to 65°C. 1102.0 grams of oxalic acid (C2H2O4(solid); 12.240 moles; SIGMA-ALDRICH®) was added to the distilled water at 65°C and dissolved quickly with stirring to form a clear, colorless solution. 656.3 grams of niobium pentoxide hydrate (Nb2O5·3.69H2O(solid): 1.975 molar equivalents of Nb2O5CBMM) was added to the aqueous oxalic acid solution at 65°C to form a white suspension. The opening of the vessel was rinsed with 1 L of distilled water to wash the powder into the solution, producing a total volume of 11 L. The 11 L of aqueous white suspension was heated and stirred at 65°C for at least 24 hours (maximum 72 hours). After heating at 65 °C for 24 hours, the solution was cooled to ambient conditions and allowed to stand (without stirring) where it appeared clear and colorless with only a small amount of white insoluble material visible. The resulting nearly clear and colorless solution was niobium oxalate solution, H3[NbO(C2O4)3] (aqueous).

[0104] A vessel was charged with 11 L of distilled water and heated to 60 °C. 4023.5 grams of vanadyl sulfate hydrate (VOSO4·3.41H2O (solid): 18.10 mol;; SIGMA-ALDRICH) was added to the 60 °C distilled water and dissolved slowly over time with vigorous stirring to form a clear blue solution. The vessel opening was rinsed with 1 L of distilled water to wash the powder into the solution, producing a total volume of 12 L of 60 °C VOSO4 (aqueous) solution.

[0105] A vessel was charged with 6 L of distilled water and heated to 60°C. 1054.6 grams of telluric acid (TeOH6(solid); 4.593 moles; SIGMA-ALDRICH) was added to the 60°C distilled water and dissolved quickly with stirring to form a clear, colorless solution. The opening of the vessel was rinsed with 1 L of distilled water to wash the powder into the solution, producing a total volume of 7 L. The 60°C, 7 L TeOH6(aqueous) solution was cooled to room temperature for use in the next step.

[0106] A jacketed glass reactor was charged with 16 L of distilled water and heated via a bath and silicone oil circulation. 16 L of distilled water was heated to 30-35°C and 4865.0 grams of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 1.4H2O (solid); 3.934 mol) was added and dissolved with stirring to form a white, slightly hazy solution. The opening of the vessel was rinsed with 1 L of distilled water to wash the powder into the solution, producing a total volume of 17 L. The entire 7 L of TeOH6 (aqueous) solution was added to a stirred flask of 30-35 °C (NH4)6Mo7O 24 4H2O (aqueous), and transferred at 412 mL / min to a turbid solution of (NH4)6Mo6TeO 24 A clear, colorless solution of (aqueous) was formed. The telluric acid container was rinsed with 1 L of distilled water, and the rinse was transferred to the glass reactor. The resulting (NH4)6Mo6TeO 24 The (aqueous) solution was heated to a target temperature of 80°C (temperature range throughout this part of the preparation was 75-85°C). (NH4)6Mo6TeO 24 After heating the (aqueous) solution to about 75°C, (NH4)6Mo6TeO 24 The pH of the (aqueous) solution is adjusted to 1680-2000 grams (density 0.91 g / cm 3 The pH was adjusted to 7.50±0.1 using 28-30% ammonium hydroxide solution (calculated to be 1.85-2.20 L). 24 The (aqueous) solution was stirred at 80° C. for 1 h. After 1 h, (NH4)6Mo6TeO 24 The temperature of the (aqueous) solution was lowered to 70-75°C in preparation for the next step, which generates a significant amount of heat. 24 The pH of the (aqueous) solution was adjusted to 1270-1550 g (density 1.85 g / cm 3 The temperature was adjusted to 7.50-5.00±0.1 using 0.69-0.84 L of 95-98% sulfuric acid, and a final solution temperature of 80-85°C was obtained even with active cooling. The acid (H2SO4) addition step and base (NH4OH) addition step both generated significant heat, which was controlled via a temperature control bath that could heat and cool the circulated silicone bath. (NH4)6Mo6TeO 24 After adjusting the (aqueous) solution to pH 5.00±0.1, the resulting (NH4)6Mo6TeO 24 The (aqueous) solution was transferred to a preheated 60 °C high-pressure reactor. The jacketed glass reactor was rinsed with 2 L of distilled water, and these rinses were transferred to a 316 stainless steel high-pressure reactor containing a special glass sleeve insert for hydrothermal reactions. (NH4)6Mo6TeO was heated to 60-80 °C. 24 The (aqueous) solution is stirred via a stirrer in a high pressure reactor.

[0107] (NH4)6Mo6TeO at 60-80°C in a stirred high pressure reactor 24 The entire amount of the vanadyl sulfate solution at 60°C was transferred to the (aqueous) solution at a rate of 367 mL / min. The vanadyl sulfate container was washed with 2 L of distilled water, and these rinses were quickly transferred to the high-pressure reactor. The resulting solution was stirred at 60-80°C for 30 minutes.

[0108] After 30 minutes, the entire volume of the room temperature niobium oxalate solution was transferred to the high-pressure reactor at approximately 60 °C at 183 mL / min to form a composite mixture containing solids and solutions of Mo, Te, V, and Nb metal oxide / salt solutions (the mixture is referred to as a slurry). The niobium oxalate container was washed with 2 L of distilled water, and these rinses were transferred to the high-pressure reactor. After all the chemicals were added, the final slurry volume in the high-pressure reactor was measured to be 62-66 L.

[0109] The high-pressure reactor was heated to 160-165°C to initiate the hydrothermal reaction. The reactor was heated externally to below 185°C to obtain a slurry temperature of 160-165°C (target 163°C). The high pressure reactor used was approximately 1000 kg and the ramp time from 60°C to 163°C was typically 5 hours. The pressure in the high pressure reactor was maintained at 95-105 psig using a back pressure regulator built into the reactor head. Note that the saturated vapor pressure of water at 163°C is 84 psig. The back pressure regulator allows excess CO, a decomposition product of oxalate / oxalic acid, to escape. x The pressure was vented to 1000 ppm. A condenser was used before the back pressure regulator to prevent excess water loss during the reaction. A tube-in-tube exchanger was used as the condenser, with the shell side cooled with water and recirculated to a cooling bath controlled at 11 °C. During the high pressure / high temperature reaction, the slurry was stirred with a paddle type agitator set at a speed sufficient to suspend the solids (150 rpm) and prevent them from settling to the bottom. Based on multiple batches produced in the examples, the measured reactor yields were 1000 ppm for the (NH) used. 46 Mo7O 24 4H2O (solid) = 1.43 kg of catalyst composition (dry, uncalcined), so the slurry concentration is about 0.11 kg 固体 / L スラリー It is.

[0110] The solids in the slurry from the hydrothermal reaction are recovered by filtration. After the hydrothermal reaction time is reached, the reactor is naturally cooled to 30-60°C before filtration. The cooling time ranges from 17-20 hours. During cooling, stirring was continued at the same speed as used during the hydrothermal reaction. The solids separated from the mother liquor are called the unwashed catalyst composition or catalyst composition (e.g., washed catalyst composition). The slurry material was transferred from the high-pressure reactor to the filter unit by cannulation. The transfer of the slurry was performed using positive air pressure less than 15 psig. The unwashed catalyst composition was washed with distilled water to remove water-soluble by-product salts including vanadium, ammonium, and sulfate compounds. The filtrate was initially blue in color and eventually became clear as the washing proceeded toward completion. A preliminary catalyst filter cake 30-35 cm deep was washed with distilled water in the ratios specified for each of the catalyst compositions 1.1-1.8, respectively.

[0111] The general procedure described above was commonly applied to the catalyst compositions 1.1-1.8 produced up to this point, except that deviations in the work-up (washing, treatment, and calcination) were made to produce different catalyst compositions 2.1-2.13 and catalyst materials (Examples 1-22).

[0112] The unwashed catalyst composition filter cake was washed with distilled water in 20-40 L increments until a total of 100-200 L (total volume as specified for each catalyst composition 1.1-1.8) was reached. As previously described, (NH4)6Mo7O 24 It was assumed that for every kg of 4H2O (solid) used, approximately 1.43 kg of precatalyst material was produced (typical dry weight yields and yields are 5.9-6.3 kg and 85-91%), and this weight was used to calculate the target amount of water required for washing, e.g., wash ratio in L of water per kg of precatalyst. For example, if 6.96 kg of theoretical precatalyst was produced and 100 L of distilled water was used to wash the solid, the wash ratio would be 14.37 L / kg.

[0113] For some catalyst compositions, qualitative and quantitative determination of sulfate residuals (and N) was performed by FTIR and CHNS analysis, respectively. Subsamples (approximately 5 g) of the catalyst compositions were taken for FTIR and CHNS analysis. The catalyst compositions were analyzed as dry solids. The solids were dried at 90° C. in a drying oven for approximately 12 hours. The dried samples have less than 2% moisture as determined by TGA-FTIR analysis at 100° C.

[0114] Figure 6 is a plot 600 of the infrared spectra of a thoroughly washed and poorly washed catalyst composition. As can be seen by comparing the spectra in Figure 2, the ammonium and sulfate peaks produce a diagnostic fingerprint, indicating that FTIR analysis can be used to validate the washing technique. FTIR revealed that the catalyst composition was not sufficiently washed and would not produce a highly active catalyst, even on a small scale calcination (e.g., less than 100 g).

[0115] Surprisingly, it was found that the catalyst compositions that yielded high activity catalysts upon large-scale calcination (e.g., greater than about 500 g) had low measured sulfur (wt%) (attributed to sulfate species). These sulfur (wt%) values ​​were below the detection limit of FTIR for sulfate. The measured sulfur (wt%) was used as a specification target for the catalyst composition resulting in high activity catalyst materials, which is crucial not only for small-scale calcination but also for large-scale calcination. In general, in the inventive examples, the weight percentages of nitrogen and sulfur in the dried catalyst composition were required to be less than 0.02 wt% for S values, whereas N was about 0.90-1.75 wt%. These specifications were achieved by either 1) extensive water washing of the catalyst composition (distilled water to catalyst ratio: 73.4 L / kg (e.g., catalyst composition 1.6 and corresponding catalyst material 4.4; Example 21)), or 2) an air treatment step (as described in some of the provided examples). Details of these workups are described in the following examples and are contrasted with comparative examples that did not undergo these workups.

[0116] <Synthesis of catalyst composition 1.1> After the hydrothermal reaction described above in the general synthesis procedure was completed, the catalyst composition slurry was transferred from the high pressure reactor (used for the hydrothermal reaction) via cannulation (positive pressure) to a filtration unit (similar to a Nutsche Pressure Filter) with a volume of about 130 L. A catalyst cake (a cylindrical cake with a diameter of 35 cm and a height of 30-35 cm) of the solid catalyst composition was formed on two sheets (one each) of polypropylene (PP) filter media by positive pressure filtration (using air pressure of up to 15 psig). The two sheets were specifically: 1) one layer of Clear Edge, woven PP filter cloth, 10.7 oz. MO / MU 7 / 1SAT HS / K 37CFM, and 2) one layer of Pope Scientific Inc, 10 micron polypropylene filter cloth, part number: 7PPVCLO10MICRON.

[0117] The catalyst cake was washed with 120 L of distilled water in three 40 L portions to remove soluble by-product slats such as ammonium and sulfate. The dark purple catalyst cake was removed from the filter unit and spread evenly into two rectangular drying pans (volume approximately 16.75 L, dimensions 48.26 x 39.05 x 8.89 cm) and a cutting tool was pressed into the cake to obtain individual cuboids of the desired dimensions once the catalyst composition was dried. The catalyst cake was dried in an oven at 90 °C for 5 days to remove excess moisture. After the catalyst cake was dried, the resulting purple solid cubes were crushed using a blade (cutting) grinder. The resulting crushed powder was catalyst composition 1.1 and weighed 6308.3 g, a weight yield of 83% (assuming a theoretical yield of 7598.07 g).

[0118] <Synthesis of catalyst composition 1.2> Catalyst composition 1.2 was prepared by the same procedure as catalyst composition 1.1, except for the following points: 1) the catalyst cake was washed with 80 L of distilled water, 40 L x 1 and 20 L x 2, 2) after the catalyst cake was dried, the resulting purple solid cubes were fed into the hopper of a jaw crusher (Retsch BB50) and the catalyst composition was crushed to a size distribution of 125-500 microns by setting the jaw gap width of the crusher to 0.5 mm, 3) the yield of the catalyst composition was slightly different at 6323.6 g, and the weight yield was 83%. Catalyst material 1.2 was analyzed by CHNS and the obtained results are shown in Table 1.1. Catalyst composition 1.2 was subjected to MRU performance test and the results are shown in Table 2.3.

[0119] <Synthesis of catalyst composition 1.3> Catalyst composition 1.3 was prepared using the same procedure as catalyst composition 1.1, except for the following: 1) the catalyst cake was washed with 100 L of distilled water, 1 x 40 L and 3 x 20 L, 2) the catalyst composition was dried in a large pot at 90°C for 7 days (no drying pan or cutting tool was used, which took longer), 3) the yield of catalyst composition was slightly different at 6233.0 g, which is a weight yield of 82%.

[0120] <Synthesis of catalyst composition 1.4> Catalyst composition 1.4 was prepared by the same procedure as catalyst composition 1.1, except for the following: 1) the catalyst cake was washed with 120 L of distilled water in three portions of 40 L each; 2) the yield of catalyst composition was slightly different at 6092.0 g, and the weight yield was 80%.

[0121] <Synthesis of catalyst composition 1.5> Catalyst composition 1.5 was prepared by the same procedure as catalyst composition 1.2. Catalyst composition 1.5 and catalyst composition 1.6 were obtained from the same preparation, but with different amounts of distilled water washing. This was achieved by washing catalyst composition 1.5 with 80 L of distilled water once at 40 L and twice at 20 L. After the 80 L volume of distilled water washing, about 67% of the wet solid catalyst composition was removed from the filter unit and finished by drying and grinding. The removed part was catalyst composition 1.5, and the remaining about 33% was further washed with distilled water to become catalyst composition 1.6.

[0122] The wet catalyst composition 1.5 was dried in an oven at 90° C. for about 5 days using the oven and drying pan / cutting tool as described above for the preparation of catalyst composition 1.1. After the catalyst composition was dried, the resulting purple solid cubes were fed into the hopper of a jaw crusher (Retsch BB50) and the catalyst composition was crushed to a size distribution of 125-500 microns by setting the jaw gap width of the crusher to 0.5 mm. The yield of catalyst composition 1.5 was about 4 kg.

[0123] The combined mass of catalyst composition 1.5 and catalyst composition 1.6 was 5970.2 g, giving a weight yield of 79%. Based on this weight yield, the wash ratio was approximately 13.4 L of distilled water per kg of solids recovered. Catalyst material 1.5 was analyzed by CHNS, and the results obtained are shown in Table 1.1.

[0124] <Synthesis of catalyst composition 1.6 (double washed)> The remaining portion of catalyst composition 1.5 was returned to the filter unit and washed with an additional 120 L of distilled water (40 L each) to produce catalyst composition 1.6. After washing with distilled water, the wet catalyst composition 1.6 was dried and crushed in a similar manner to composition 1.5, e.g., dried in an oven using a drying pan / cutting tool and crushed using a jaw crusher with a jaw gap width of 0.5 mm. The yield of catalyst composition 1.6 was about 2 kg. Based on this weighed yield and a previous wash of 13.4 L / kg, the wash ratio for about 2 kg of catalyst composition 1.6 was about 73.4 L of distilled water per kg of solids recovered (120 L / 2=60 L; 60 L+13.4 L=73.4 L). The combined mass of catalyst compositions 1.5 and 1.6 was 5970.2 g, giving a weight yield of 79%. Catalyst material 1.6 was analyzed by CHNS and the results obtained are shown in Table 1.1.

[0125] <Synthesis of catalyst composition 1.7> Catalyst composition 1.7 was prepared by the same procedure as catalyst composition 1.1, except for the following: 1) the catalyst cake was washed with 100 L of distilled water, 40 L x 1 and 20 L x 3 times; 2) after the catalyst cake was dried, the resulting purple solid cubes were fed into the hopper of a jaw crusher (Retsch BB50) and the catalyst composition was crushed to a size distribution of 125-500 microns by setting the jaw gap width of the crusher to 0.5 mm; 3) the yield of the catalyst composition was slightly different at 5877 g, and the weight yield was 77%. It is noted that catalyst composition 1.7 used 18.01 moles (4043 g) of VOSO4 salt during the hydrothermal reaction step. Catalyst material 1.7 was analyzed by CHNS and the results are shown in Table 1.1.

[0126] <Synthesis of catalyst composition 1.8 (reduced V loading)> Catalyst composition 1.8 was prepared using the same procedure as catalyst composition 1.7, except that the amount of VOSO4·3.41H2O salt was reduced from 18.01 mol (4043 g) to 15.08 mol (3369 g), i.e., the vanadium loading was reduced by about 16%. The remaining workup (washing, drying, and grinding) was the same as for catalyst composition 1.8.

[0127] The reduced vanadium loading resulted in a theoretical catalyst yield of 3369 g VOSO4·3.41H2O (15.08 mol) with a corresponding theoretical weight yield of V2O5 = 1371.4 g V2O5 (7.54 mol). Thus, a mass reduction of approximately 267 g of V2O5 is expected for catalyst composition 1.8 compared to catalyst composition 1.7 (1638-1371). This mass reduction corresponds to a theoretical yield of 7331.07 g of mixed metal oxide oxide.

[0128] The weight yield of catalyst composition 1.8 was 6062 g after drying and grinding, assuming a theoretical yield of 7331.07 g, the weight yield was 83%. Catalyst composition 1.8 was analyzed by CHNS and the results obtained are shown in Table 1.1.

[0129] Analysis of C, N, and S (wt%) by CHNS for catalyst compositions 1.1 to 1.8. [Table 2]

[0130] <Treated catalyst compositions 2.1 to 2.13 (samples treated with air at 330°C and 250°C)>

[0131] [Example 1] Synthesis of catalytic composition 2.1 (AT 330°C, 1 hour) (AT is air treatment) A portion of the total mass of catalyst composition 1.1 was loaded into three quartz boats (semi-cylindrical with a diameter of about 13 cm, a depth of about 6.4 cm, and a length of about 32.3 cm). Each boat contained approximately the same volume (about 1224 cm). 3 ) of catalyst composition was loaded into the quartz boat for a total loading mass of 3288.8 g of catalyst composition 1.1 (i.e., before treatment to form catalyst composition 2.1). The quartz boat containing the catalyst composition was loaded into a quartz tube for hot air treatment followed by a hot nitrogen calcination. The quartz tube had a length of 180 cm and an inner diameter of 14 cm. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW and included a built-in thermocouple and temperature control programming capability. The quartz tube was sealed with a flange and the tube was purged with 2 psig bulk nitrogen (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The outlet side of the tube was evacuated through a water bubbler, which was used to prevent backflow of air and maintain an anaerobic atmosphere in the tube. The nitrogen purge was continued for 8 hours, after which the tube was heated to 330°C at a rate of 1.6°C / min and then held at 330°C for approximately 30 minutes. After 30 minutes at 330°C, the furnace was turned off and the entire tube was immediately exposed to the atmosphere by removing the inlet flange (to avoid overcooling the tube) and allowing natural draft to diffuse the air into the tube. The air treatment at 330°C was estimated to be 1 hour. The entire calcination apparatus was allowed to cool to room temperature overnight to produce catalyst composition 2.1. Catalyst composition 2.1 was not removed from the quartz tube for weighing or characterization, but was treated by calcination to produce catalyst material 2.1 according to the procedure discussed in Example 1B.

[0132] [Example 2] Synthesis of catalyst composition 2.2 (AT 330°C, 2 hours) Approximately 17 g of catalyst composition 1.2 was loaded into an 8 dram glass vial and aired in a muffle furnace at 330° C. for 2 hours to form catalyst composition 2.2. The muffle furnace was heated in air to a target temperature of 330° C. in 45 minutes. Catalyst composition 2.2 was treated by calcination according to the procedure discussed in Example 2B to produce catalyst material 1.1. Catalyst composition 2.2 was analyzed by CHN, the results of which are shown in Table 2.1. Catalyst composition 2.2 was subjected to MRU performance testing, the results of which are shown in Table 2.3.

[0133] [Example 3] Synthesis of catalyst composition 2.3 (AT 330°C, 6 hours) Approximately 17 g of catalyst composition 1.2 was loaded into an 8 dram glass vial and aired in a muffle furnace at 330° C. for 6 hours to form catalyst composition 2.3. The muffle furnace was heated in air to a target temperature of 330° C. in 45 minutes. Catalyst composition 2.3 was treated by calcination according to the procedure discussed in Example 3B to produce catalyst material 1.2. Catalyst composition 2.3 was analyzed by CHN, the results of which are shown in Table 2.1. Catalyst composition 2.3 was subjected to MRU performance testing, the results of which are shown in Table 2.3.

[0134] [Example 4] Synthesis of catalyst composition 2.4 (AT 330°C, 12 hours) A 907.9 g portion of catalyst composition 1.2 was loaded into a single quartz boat (half-cylinder with a diameter of about 13 cm, a depth of about 6.4 cm, and a length of about 32.3 cm). The quartz boat containing the catalyst composition was loaded into a muffle furnace and heated in air to a target temperature of 330° C. in 45 minutes. The furnace was held at 330° C. under air for 12 hours, after which the furnace was allowed to cool to room temperature overnight. The resulting 330° C. air treated material is catalyst composition 2.4. Catalyst composition 2.4 was treated by calcination according to the procedure discussed in Example 4B to produce catalyst material 2.2. Catalyst composition 2.4 was analyzed by CHN, the results of which are shown in Table 2.1. Catalyst composition 2.4 was subjected to MRU performance testing, the results of which are shown in Table 2.3.

[0135] [Example 5] Synthesis of catalyst composition 2.5 (AT 330°C, 12 hours) Catalyst composition 2.5 is formed from a 17 g subsample of 1381.25 g of catalyst composition 2.4. Catalyst composition 2.5 was used in a small scale calcination according to the procedure discussed in Example 5B to produce catalyst material 1.3.

[0136] [Example 6] Synthesis of catalyst composition 2.6 (AT 330°C, 3 hours) A portion of the total mass of catalyst composition 1.3 was loaded into two quartz boats (semi-cylindrical with a diameter of about 13 cm, a depth of about 6.4 cm, and a length of about 32.3 cm). Each boat contained approximately the same volume (about 1224 cm). 3 ) of catalyst was loaded, with the total loaded mass of all three boats being 2905.0 g of catalyst composition 1.3. Catalyst composition 1.3 was further dried overnight at 90° C. in a convection oven. The dry weight of catalyst composition 1.3 was 2873.5 g (dry mass). The quartz boat containing the catalyst composition was loaded into a quartz tube for hot air treatment followed by a high temperature nitrogen bake. The quartz tube was 180 cm long and had an internal diameter of 14 cm. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW and included an integrated thermocouple and temperature control programming capability. The quartz tube was sealed with a flange and left under a stagnant air atmosphere. The outlet side of the tube was evacuated through a water bubbler, and the inlet side of the tube was the nitrogen source for the calcination step. Under stagnant air, the furnace was heated to 330°C at a rate of 1.6°C / min. After the temperature reached 330°C (within about 3 hours), the inlet side of the quartz tube was purged with 2 psig bulk nitrogen (less than 10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeter). The air treatment step of catalyst composition 1.3 formed catalyst composition 2.6. Catalyst composition 2.6 was not isolated or weighed, but instead was immediately treated by a nitrogen calcination step according to the procedure discussed in Example 6B to produce catalyst material 2.3.

[0137] [Example 7] Synthesis of catalyst composition 2.7 (AT 250 ° C, less than 1 hour) A 2356.9 g portion of catalyst composition 1.3 was loaded into a quartz boat (half-cylinder with a diameter of about 13 cm, a depth of about 6.4 cm, and a length of about 32.3 cm). The quartz boat containing the catalyst composition was loaded into a convection oven and further dried overnight at 90° C. After catalyst composition 1.3 was cooled, the dry weight was recorded as 2322.9 g. The dried catalyst composition 1.3 was then placed back into the convection oven and heated in air to a target temperature of 250° C. in less than 1 hour. After the temperature in the oven reached 250° C., the oven was turned off and allowed to cool to room temperature overnight. The resulting air-treated material (250° C. for less than 1 hour) is catalyst composition 2.7. Catalyst composition 2.7 was treated by calcination according to the procedure discussed in Example 7B to produce catalyst material 2.4.

[0138] [Example 8] Synthesis of catalyst composition 2.8 (AT 250°C, 5 hours) A 966.9 g portion of catalyst composition 1.3 was loaded into a single quartz boat (half-cylindrical with a diameter of about 13 cm, a depth of about 6.4 cm, and a length of about 32.3 cm). The quartz boat containing the catalyst composition was loaded into a convection oven and further dried overnight at 90° C. After catalyst composition 1.3 was cooled to ambient temperature, e.g., about 21° C., the dry weight was recorded as 940.0 g. The dried catalyst composition 1.3 was then placed back into the convection oven and heated in air to a target temperature of 250° C. in less than 1 hour. After the temperature in the oven reached 250° C., the oven was left at 250° C. for 5 hours, after which the oven was turned off and allowed to cool to room temperature overnight. The resulting air-treated material (approximately 5 hours at 250° C.) is catalyst composition 2.8. Catalyst composition 2.8 was treated by calcination according to the procedure discussed in Example 8B to produce catalyst material 2.5.

[0139] [Example 9] Synthesis of catalyst composition 2.9 (AT 250°C, 6 hours) A 3075.6 g portion of catalyst composition 1.4 was loaded into three quartz boats (semi-cylindrical, approximately 13 cm in diameter, approximately 6.4 cm deep, and approximately 32.3 cm long). Each boat contained approximately the same volume (approximately 1224 cm 3 The quartz boat containing the catalyst composition was loaded into a convection oven and further dried at 90° C. overnight. The dried catalyst composition 1.4 was then placed back into the convection oven and heated in air to a target temperature of 250° C. in less than 1 hour. After the temperature in the oven reached 250° C., the oven was left at this target temperature of 250° C. for 6 hours, after which the oven was turned off and allowed to cool to room temperature overnight. The resulting air-treated material (approximately 6 hours at 250° C.) was catalyst composition 2.9, which weighed 3043.9 g and had a mass loss of only 1% upon air treatment at 250° C. Catalyst composition 2.9 was treated by calcination according to the procedure discussed in Example 9B to produce catalyst material 2.6.

[0140] [Example 10] Synthesis of catalyst composition 2.10 (AT 250°C, 6 hours) The remaining 1641.7 g of catalyst composition 1.4 was loaded into two quartz boats and air treated using the same equipment and procedure outlined for catalyst composition 2.9 (i.e., the procedure was replicated to demonstrate the reproducibility of results using this procedure). The resulting material was air treated at 250° C. for about 6 hours to produce catalyst composition 2.10, which weighed 1611.2 g and had a mass loss of only 2% upon air treatment at 250° C. Catalyst composition 2.10 was treated by calcination according to the procedure discussed in Example 10B to produce catalyst material 2.7.

[0141] [Example 11] Synthesis of catalyst composition 2.11 (double washed, AT250°C, 6 hours) 1138 g of catalyst composition 1.6 was loaded into a single quartz boat and air treated using the same equipment and procedure outlined for catalyst composition 2.9. The resulting air treated material (250°C for approximately 6 hours) is catalyst composition 2.11. Catalyst composition 2.11 was treated by calcination according to the procedure discussed in Example 11B to produce catalyst material 2.8. Catalyst composition 2.11 was analyzed by CHN and the results are shown in Table 2.2.

[0142] [Example 12] Synthesis of catalyst composition 2.12 (AT 250°C, 6 hours) A total of 5877 g of catalyst composition 1.7 was calcined in two calcinations of equal portions (approximately 2939 g each). Both calcinations were performed in three quartz boats to process the entire batch of catalyst composition 1.7. Prior to the nitrogen calcination step, catalyst composition 1.7 was air treated using the same equipment and procedure outlined for catalyst composition 2.9. The resulting air treated material (approximately 6 hours at 250° C.) was catalyst composition 2.12. Catalyst composition 2.12 was treated by calcination according to the procedure discussed in Example 12B to produce catalyst material 2.9. Catalyst composition 2.12 was analyzed by CHN and the results are shown in Table 2.2.

[0143] [Example 13] Synthesis of catalyst composition 2.13 (AT 250°C, 6 hours) Of the total 6062 g (83%) of catalyst composition 1.8, 5022 g was calcined in two calcinations. Prior to the nitrogen calcination step, catalyst composition 1.8 was air treated using the same equipment and procedure outlined for catalyst composition 2.9. The resulting air treated material (approximately 6 hours at 250° C.) was catalyst composition 2.13. Catalyst composition 2.13 was calcined according to the procedure discussed in Example 13B to produce catalyst material 2.10.

[0144] Analysis of N (wt%) by CHNS for catalyst compositions 1.2 and 2.2 to 2.4. [Table 3] Subsamples of each catalyst composition were taken to perform MRU testing, and the remainder of the samples were worked up into catalyst material by nitrogen calcination at 600° C. Catalyst compositions 1.2, and 2.2-2.4 were all prepared from catalyst composition 1.2.

[0145] Analysis of N (wt%) by CHNS for catalyst compositions 2.11-2.12. [Table 4] Subsamples of each catalyst composition were taken to perform MRU testing, and the remainder of the samples were then worked up to catalytic materials in a nitrogen calcination at 600°C.

[0146] Analysis of activity and selectivity of catalyst materials 1.2 and 2.2-2.4 to ethane to ethylene. [Table 5] Subsamples of each catalyst composition were taken to perform MRU testing, and the remainder of the samples were worked up into catalyst material by nitrogen calcination at 600° C. Catalyst compositions 1.2, and 2.2-2.4 were all prepared from the same catalyst composition 1.2.

[0147] Calcination of catalyst materials 1.1-1.3 (air treatment at 330°C before small-scale nitrogen calcination)

[0148] [Example 2B] Synthesis of catalytic material 1.1 (AT 330°C, 2 hours) 7.34 g of catalyst composition 2.2 was placed in a quartz boat (semi-cylindrical, approximately 1.4 cm in diameter, 1.3 cm deep, and 69 cm long; volume approximately 10-11 cm). 3 ) and loaded into a quartz tube approximately 2 feet long with an internal diameter of approximately 2.5 cm. The quartz tube was connected to a nitrogen purge system via ground glass fittings with a nitrogen gas source on the inlet side and a water bubbler (used to keep the quartz tube under anaerobic atmosphere) on the outlet side. Bulk nitrogen (<10 ppm oxygen) was flowed through the quartz tube at 85 sccm (standard cubic centimeters) for 8 hours. After 8 hours, the bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear™ Gas Purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 85 sccm overnight. The flow rate was reduced from 85 sccm to 30 sccm and the tube furnace heater was turned on. The tube furnace heating was applied with the following program: 1) Ramp from room temperature to 600°C over 6 hours (ramp rate 1.6°C / min); 2) The controller holds the temperature at 600°C for 2 hours; 3) Turn off the furnace and cool the apparatus to room temperature. After calcination, the resulting catalyst material 1.1 was black in color and weighed 7.00 g, which corresponds to a calcination weight yield of 95%. The catalyst material 1.1 was subjected to MRU performance testing, and the results are shown in Table 2.1.

[0149] [Example 3B (continued)] Synthesis of catalyst material 1.2 (AT 330°C, 6 hours) 7.45 g of catalyst composition 2.3 was calcined according to the same procedure and equipment as described for catalyst material 1.1. After calcination, the resulting catalyst material 1.2 was black in color and weighed 7.19 g, which corresponds to a calcination weight yield of 97%. Catalyst material 1.2 was subjected to MRU performance testing, the results of which are shown in Table 2.1.

[0150] [Example 5B (continued)] Synthesis of catalyst material 1.3 (AT 330°C, 12 hours) 6.86 g of catalyst composition 2.5 (same base material as catalyst composition 2.4) was calcined according to the same procedure and equipment as described for catalyst material 1.1. After calcination, the resulting catalyst material 1.3 was black in color and weighed 6.68 g, which corresponds to a calcination weight yield of 97%. Catalyst material 1.3 was subjected to MRU performance testing, the results of which are shown in Table 2.1.

[0151] Analysis of activity and selectivity of catalyst materials 1.1-1.3 for ethane to ethylene. [Table 6] Catalyst material 3.2 was prepared with only nitrogen treatment at 600° C., ie, without air treatment at 330° C. Catalyst materials 1.1-1.3 and 3.3 were all prepared from the same base catalyst composition 1.2.

[0152] Calcination of catalyst materials 2.1-2.13 (air treatment at 330°C or 250°C before large-scale nitrogen calcination)

[0153] [Example 1B] Synthesis of catalytic material 2.1 (AT 330°C, 1 hour) The quartz tube was resealed with a flange connection and Catalyst Composition 2.1 was purged with bulk nitrogen at 2 psig (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The outlet side of the tube was evacuated through a water bubbler to keep the tube under anaerobic atmosphere and prevent air backflow. After purging the quartz tube with bulk nitrogen for approximately 3.5 hours, the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tubular furnace was used to calcinate the catalyst composition 2.1 into catalyst material 2.1 using the following heating program: 1) ramp up to 250°C at 1.6°C / min and hold at this temperature for 1 hour; 2) ramp up to 300°C at 1.6°C / min and hold at this temperature for 1 hour; 3) ramp up to a final temperature of 600°C at 1.6°C / min and hold for 10 hours; 4) cool down to 100°C at 1.6°C / min; 5) turn off the furnace and allow the device to cool to room temperature. The resulting black catalyst material 2.1 was removed from the calcination device with a total weight of 3072.2 g, representing a calcination weight yield of 93.4% (compared to the weight of the catalyst composition 2.1 initially loaded). Catalyst material 2.1 was analyzed by ICP-MS, the results of which are shown in Tables 3.4 and 3.5. Catalyst material 2.1 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0154] [Example 4B] Synthesis of catalytic material 2.2 (AT 330°C, 12 hours) Catalyst composition 2.4 was loaded midway into the quartz tube in the same quartz boat used for the 330°C air treatment in the muffle furnace. The quartz tube was 180 cm long with an inside diameter of 14 cm. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, a built-in thermocouple, and temperature control programming. The quartz tube was sealed with a flange and the tube was purged with 2 psig bulk nitrogen (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The outlet side of the tube was evacuated through a water bubbler. The water bubbler was used to maintain an anaerobic atmosphere in the tube (i.e., by preventing backflow of air). The quartz tube was purged with bulk nitrogen for approximately 1 hour, after which the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tube furnace was used to calcinate catalyst composition 2.4 into catalyst material 2.2 using the following heating program: 1) ramp to 600°C at 1.6°C / min rate; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the apparatus to room temperature. The resulting 885.9 g of black powder was catalyst material 2.2, a mass yield of 98% based on 907.9 g of catalyst composition 1.2 used. Catalyst material 2.2 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0155] [Example 6B] Synthesis of catalytic material 2.3 (AT 330°C, 3 hours) Catalyst composition 2.6 in a quartz tube was purged with 2 psig bulk nitrogen (<10 ppm oxygen, 1000 sccm flow rate) at a temperature of 330° C. for about 4 hours. Catalyst composition 2.6 was then purged with purified nitrogen at 330° C. and 1000 sccm flow rate for 20 hours. The inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​to produce purified nitrogen (<1 ppm oxygen) used to purge the quartz tube. Catalyst composition 2.6 was calcined using the following heating program to form catalyst material 2.3: 1) 330° C. to 600° C. at a rate of 1.6° C. / min; 2) hold at 600° C. for 4 hours; 3) turn off the furnace and cool the apparatus to room temperature. The resulting black powder was catalyst material 2.3, with a yield of 2669.4 g and a calcination mass yield of 93% (based on the initial dry mass of catalyst composition 1.3). Catalyst material 2.3 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0156] [Example 7B] Synthesis of catalytic material 2.4 (AT 250°C, less than 1 hour) The quartz boat containing the treated catalyst composition 2.7 was loaded into a quartz tube for hot air treatment followed by a hot nitrogen calcination. The quartz tube was 180 cm long with an internal diameter of 14 cm. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, a built-in thermocouple, and temperature control programming. The quartz tube was sealed with a flange and the tube was purged with bulk nitrogen at 2 psig (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The exit side of the tube was evacuated through a water bubbler. The water bubbler was used to prevent air backflow and maintain an anaerobic atmosphere in the tube. The quartz tube was purged with bulk nitrogen from the inlet side for about 5 hours, after which the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tube furnace was used to calcinate catalyst composition 2.7 to catalyst material 2.4 using the following heating program: 1) ramp from room temperature to 600°C at a rate of 1.6°C / min; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the device to room temperature. The resulting black powder was catalyst material 2.4, which weighed 2141.2 g and had a calcination mass yield of 92% (based on the initial dry mass of catalyst composition 1.3). Catalyst material 2.4 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0157] [Example 9B] Synthesis of catalytic material 2.6 (AT 250°C, 6 hours) The quartz boat containing the treated catalyst composition 2.9 was loaded into a quartz tube for hot air treatment followed by a hot nitrogen calcination. The quartz tube was 180 cm long with an internal diameter of 14 cm. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, a built-in thermocouple, and temperature control programming. The quartz tube was sealed with a flange and the tube was purged with bulk nitrogen at 2 psig (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The exit side of the tube was evacuated through a water bubbler. The water bubbler was used to prevent air backflow and maintain an anaerobic atmosphere in the tube. The quartz tube was purged with bulk nitrogen from the inlet side for about 1 hour, then the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm for 6 hours. Catalyst composition 2.9 was calcined in a tube furnace to give catalyst material 2.3 using the following heating program: 1) ramp to 600°C at 1.6°C / min rate; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the device to room temperature. The resulting black powder was catalyst material 2.6, which weighed 2874.4g and had a calcination mass yield of 94% (based on the air-treated catalyst composition 2.9 mass). Catalyst material 2.6 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0158] [Example 8B] Synthesis of catalyst material 2.5 (AT250°C, 5 hours) The quartz boat containing the catalyst composition 2.8 was loaded into a quartz tube for hot air treatment and subsequent high temperature nitrogen calcination. The subsequent nitrogen purge and calcination steps to convert the catalyst composition 2.8 into the catalyst material 2.5 were the same as those applied to calcinate the catalyst composition 2.7 into the catalyst material 2.4. After calcination at 600°C under nitrogen for 6 hours, the obtained black powder was the catalyst material 2.5, which weighed 875.2g and had a calcination mass yield of 94% (based on the initial dry mass of the catalyst composition 1.3). The catalyst material 2.5 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0159] [Example 10B] Synthesis of catalytic material 2.7 (AT 250 ° C, 6 hours) The quartz boat containing catalyst composition 2.10 was loaded into a quartz tube for high temperature air treatment and subsequent high temperature nitrogen calcination. The subsequent nitrogen purge and calcination steps to convert catalyst composition 2.10 to catalyst material 2.7 were the same as those applied to calcinate catalyst composition 2.6 to catalyst material 2.6. This was a repeat procedure to confirm the reproducibility of the results. After calcination at 600°C under nitrogen for 6 hours, the resulting black powder was catalyst material 2.7, weighing 1542.6g, with a calcination mass yield of 96% (based on the air-treated catalyst composition 2.10 mass). Catalyst material 2.7 was subjected to MRU performance testing, the results of which are shown in Table 3.6.

[0160] [Example 11B] Synthesis of catalyst material 2.8 (double washed, AT250°C, 6 hours) The quartz boat containing the catalyst composition 2.11 was loaded into a quartz tube for hot air treatment and subsequent high temperature nitrogen calcination. The subsequent nitrogen purge and calcination steps to convert the catalyst composition 2.11 into the catalyst material 2.8 were the same as those applied to calcinate the catalyst composition 2.6 into the catalyst material 2.6. After calcination at 600°C under nitrogen for 6 hours, the resulting black powder was the catalyst material 2.8, which weighed 1063g, and the calcination mass yield was 93% based on the 1138g of the catalyst composition 1.6 used in this procedure. The catalyst material 2.8 was analyzed by CHN, and the results are shown in Table 3.1. The catalyst material 2.8 was also subjected to MRU performance testing, and the results are shown in Table 3.6.

[0161] [Example 12B] Synthesis of catalyst material 2.9 (normally washed, AT250°C, 6 hours) Two approximately equal portions of catalyst composition 2.12 treated at 250°C for about 6 hours were calcined in two batches, working up about 6 kg of solids. In each calcination, three quartz boats containing catalyst composition 2.12 were loaded into a quartz tube for high temperature nitrogen calcination. The subsequent nitrogen purge and calcination steps to convert catalyst composition 2.12 to catalyst material 2.9 were the same as those applied to calcinate catalyst composition 2.6 to catalyst material 2.6. After two calcinations at 600°C under nitrogen, the total mass of the resulting black powder was 5481 g of catalyst material 2.9, a calcination mass yield of 93% based on 5877 g of catalyst composition 1.7 used in this procedure. 5481 g of product was recovered, giving an overall weight yield of catalyst material 2.9 of 72% (assuming a theoretical yield of 7598.07 g based on the mass of chemicals used for catalyst composition 1.7). Catalyst material 2.9 was analyzed by CHN and the results are shown in Table 3.1. Catalyst material 2.9 was also analyzed by ICP-MS and the results are shown in Tables 3.2 and 3.3. Additionally, catalyst material 2.9 was subjected to MRU performance testing and the results are shown in Table 3.6.

[0162] [Example 13B] Synthesis of catalyst material 2.10 (V reduction, normal cleaning, AT250°C, 6 hours) Two portions of catalyst composition 2.13 were calcined in two batches to work up about 5 kg of solids. In each calcination, the quartz boat containing catalyst composition 2.13 was loaded into a quartz tube for high-temperature nitrogen calcination. The subsequent nitrogen purge and calcination steps to convert catalyst composition 2.13 into catalyst material 2.10 were the same as those applied to calcinate catalyst composition 2.6 into catalyst material 2.6. After calcining twice at 600°C under nitrogen, the total mass of the black powder obtained was 4601 g of catalyst material 2.10, and the calcination mass yield was 92%, based on 5022 g of catalyst composition 1.8 used in this procedure. 5022 g of product was recovered and the overall weight yield of Catalyst Material 2.9 was estimated to be 80% (theoretical yield of 7598.07 multiplied by 83% equals 6306.40 g; assuming the mass of chemicals used for Catalyst Composition 1.8 minus the 17% portion of recovered solid product used to produce Catalyst Material 4.5). The approximately 8% improvement in mass yield for Example 13 compared to Example 12 (estimated 80% vs. 72%) is likely due to the reduced amount of VOSO4 starting material used in Catalyst Composition 1.8. Catalyst Material 2.10 was analyzed by ICP-MS and the results are shown in Tables 3.2 and 3.3. Catalyst Material 2.10 was also subjected to MRU performance testing and the results are shown in Table 3.6.

[0163] Analysis of N (wt%) by CHN for catalyst materials 2.8 and 2.9. [Table 7]

[0164] Analysis of the concentrations and molar ratios of Mo, V, Nb, and Te by ICP-MS in catalyst materials 2.1 and 2.9–2.10. [Table 8]

[0165] [Table 9]

[0166] [Table 10] Catalyst materials 2.1, 3.1 and 4.1 were all generated from a common catalyst composition 1.1, but were worked up in different ways to produce the final catalyst materials.

[0167] [Table 11] Catalyst materials 2.1, 3.1 and 4.1 were all generated from a common catalyst composition 1.1 but were worked up in different ways to produce the final catalyst materials. The molar ratios were calculated based on the ICP-MS results shown in Table 3.4. The molar ratios are relative to the moles of Mo.

[0168] Analysis of activity and selectivity of catalyst materials 2.1-2.10 from ethane to ethylene. [Table 12] Catalyst materials 2.1-2.10 were prepared in quantities greater than 900 g. The results in this table, compared to catalyst materials 3.X (Table 4.3) and 4.X (Table 5.4), demonstrate the importance of meeting the S (wt%) specification of less than about 0.02 wt%. As described herein, this can be accomplished through air treatment or through thorough washing during filtration for large scale calcined material, e.g., greater than about 1 kg. Furthermore, the results demonstrate that the catalyst composition is sensitive to both the temperature and time used in the air treatment step.

[0169] 3.1-3.4 Calcination of catalytic materials (no air treatment before small-scale nitrogen calcination)

[0170] [Example 14] Synthesis of catalyst material 3.1 (without AT) A representative small-scale calcination (less than 100 g) of catalyst material 3.1 was carried out by dispensing a portion (20-30 g) of catalyst composition 1.1 in a quartz boat (semi-cylindrical, approximately 4 cm in diameter, 2.0 cm deep, and 9.5 cm long, with a volume of approximately 52 cm). 3 ). The quartz boat was loaded into a quartz tube approximately 144 cm long and 5.1 cm inside diameter. The quartz tube was connected to a nitrogen purge system via ground glass fittings, with the inlet side being a nitrogen gas source and the outlet side vented to the laboratory ventilation header. Bulk nitrogen (<10 ppm oxygen) was flowed through the quartz tube at 400 sccm (standard cubic centimeters) for 8 hours. After 8 hours, the bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 400 sccm for approximately 12 more hours. The tube furnace used for firing at this scale had a maximum nameplate furnace wattage of 15.65 KW and the ability to program custom temperature heating profiles. The tube furnace heating was applied with the following program: 1) ramp from room temperature to 600°C over 6 hours (ramp rate is 1.6°C / min); 2) hold the temperature at 600°C for 2 hours; 3) turn off the furnace and cool the device to room temperature. After calcination, the black powder obtained was catalyst material 3.1. The typical calcination mass yield was above about 85 wt%. Catalyst material 3.1 was analyzed by ICP-MS, and the results are shown in Tables 4.1 and 4.2. Catalyst material 3.1 was also subjected to MRU performance testing, and the results are shown in 4.3.

[0171] [Example 15] Synthesis of catalyst material 3.2 (without AT) The following small-scale calcination (<20 g) was representative of a typical calcination: 6.78 g of catalyst composition 1.2 was placed in a quartz boat (semi-cylindrical, approximately 1.4 cm in diameter, 1.3 cm deep, and 6.9 cm long; volume approximately 10-11 cm). 3 ) and loaded into a quartz tube approximately 2 feet long with an internal diameter of approximately 2.5 cm. The quartz tube was connected to a nitrogen purge system via ground glass fittings, with a nitrogen gas source on the inlet side and a water bubbler (used to keep the quartz tube under anaerobic atmosphere) on the outlet side. Bulk nitrogen (<10 ppm oxygen) was flowed through the quartz tube at 85 sccm (standard cubic centimeters) for 8 hours. After 8 hours, the bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 85 sccm overnight. The flow rate was reduced from 85 sccm to 30 sccm and the tube furnace heater was turned on. The tubular furnace heating was applied with the following program: 1) ramp from room temperature to 600 °C over 6 h (ramp rate is 1.6 °C / min); 2) hold the temperature at 600 °C for 2 h; 3) turn off the furnace and cool the sample to room temperature. After calcination, the obtained catalyst material 3.2 is black in color and weighs 6.07 g, which corresponds to a calcination weight yield of 90%. The catalyst material 3.2 was subjected to MRU performance test, the results of which are shown in 4.3.

[0172] [Example 16] Synthesis of catalyst material 3.3 (without AT) Catalyst composition 1.3 was calcined to give catalyst material 3.3 using the same general procedure as described for catalyst material 3.2. Catalyst material 3.3 was subjected to MRU performance testing, the results of which are shown in 4.3.

[0173] [Example 17] Synthesis of catalyst material 3.4 (without AT) Catalyst composition 1.4 was calcined to give catalyst material 3.4 using the same general procedure as described for catalyst material 3.1. Catalyst material 3.4 was analyzed by ICP-MS, the results of which are shown in Tables 4.1 and 4.2. Catalyst material 3.4 was subjected to MRU performance testing, the results of which are shown in 4.3.

[0174] Analysis of the concentrations and molar ratios of Mo, V, Nb, and Te by ICP-MS for catalyst materials 3.1 and 3.4. [Table 13]

[0175] [Table 14]

[0176] Analysis of activity and selectivity of catalyst materials 3.1-3.4 from ethane to ethylene. [Table 15] Catalyst materials 3.1-3.4 were prepared in quantities less than 100 g. The results in this table, compared to catalyst materials 2.X (Table 3.6) and 4.X (Table 5.4), illustrate the importance of meeting the S (wt%) specification of less than about 0.02 wt%. As described herein, this can be achieved for large scale calcined material, e.g., greater than about 1 kg, through air treatment or thorough washing during filtration.

[0177] Catalyst material calcination 4.1-4.5 (no air treatment before large-scale nitrogen calcination)

[0178] [Example 18] Synthesis of catalyst material 4.1 (without AT) 2764.9 g of catalyst composition 1.1 was loaded in approximately equal portions between three quartz boats (half-cylindrical, approximately 13 cm in diameter, 6.4 cm deep, and 32.3 cm long). The quartz boats with catalyst composition were loaded into a convection oven and further dried overnight at 90° C. After cooling, the dry weight of catalyst composition 1.3 was recorded as 2669.9 g. The quartz boat was loaded into the middle of the quartz tube. The quartz tube was approximately 180 cm long and 14 cm inside diameter. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, with built-in thermocouple and temperature control programming capability. The quartz tube was sealed with a flange and the tube was purged with 2 psig bulk nitrogen (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The outlet side of the tube is vented through a water bubbler. This water bubbler is used to keep the tube in an anaerobic atmosphere (i.e., prevent air backflow). After purging the quartz tube with bulk nitrogen for approximately 4 hours, the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tube furnace calcined Catalyst Composition 1.1 to Catalyst Material 4.1 using the following heating program: 1) ramp to 600°C at a rate of 1.6°C / min; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the apparatus to room temperature. The resulting 2495.1 g black powder was Catalyst Material 4.1, with a calcined mass yield of 93.4%. Catalyst Material 4.1 was analyzed by ICP-MS and the results are shown in Tables 5.2 and 5.3. Catalyst material 4.1 was subjected to MRU performance testing, the results of which are shown in 5.4.

[0179] [Example 19] Synthesis of catalyst material 4.2 (without AT) 926 g of catalyst composition 1.2 was loaded into a single quartz boat (half-cylindrical, approximately 13 cm in diameter, 6.4 cm deep, and 32.3 cm long). The quartz boat was loaded into the middle of the quartz tube. The quartz tube was approximately 180 cm long and 14 cm inside diameter. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, a built-in thermocouple, and temperature control programming. The quartz tube was sealed with a flange and the tube was purged with 2 psig bulk nitrogen (less than 10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The exit side of the tube was evacuated through a water bubbler. The water bubbler was used to prevent air backflow and maintain an anaerobic atmosphere in the tube. The quartz tube was purged with bulk nitrogen for approximately 1 hour, after which the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tube furnace was used to calcinate catalyst composition 1.2 to catalyst material 4.2 using the following heating program: 1) ramp to 600°C at a rate of 1.6°C / min; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the apparatus to room temperature. The resulting 861 g black powder was catalyst material 4.2, with a calcination mass yield of 93%. Catalyst material 4.2 was subjected to MRU performance testing, the results of which are shown in 5.4.

[0180] [Example 20] Synthesis of catalyst material 4.3 (normally washed, no AT) 2006 g of catalyst composition 1.5 was charged in two approximately equal portions into two quartz boats (half-cylindrical, approximately 13 cm in diameter, 6.4 cm deep, and 32.3 cm long). The quartz boats with catalyst composition were loaded into a convection oven and further dried at 90° C. overnight. After the dried catalyst composition 1.5 was cooled, the quartz boat was loaded into the center of a quartz tube. The quartz tube was approximately 180 cm long and 14 cm inside diameter. The tube furnace was a Carbolite Gero GHA12 / 1200 with a maximum nameplate wattage of 7.02 kW, an integrated thermocouple, and temperature control programming capabilities. The quartz tube was sealed with a flange and the tube was purged with 2 psig bulk nitrogen (<10 ppm oxygen) at a flow rate of 1000 sccm (standard cubic centimeters). The outlet side of the tube is vented through a water bubbler. This water bubbler is used to keep the tube in an anaerobic atmosphere (i.e., prevent air backflow). After purging the quartz tube with bulk nitrogen for approximately 4 hours, the inlet bulk nitrogen was redirected through an oxygen trap (LabClear Oxiclear gas purifier) ​​and the quartz tube was purged with purified nitrogen (<1 ppm oxygen) at 1000 sccm overnight. The tube furnace calcined catalyst composition 1.5 to catalyst material 4.3 using the following heating program: 1) ramp to 600°C at 1.6°C / min rate; 2) hold at 600°C for 6 hours; 3) turn off the furnace and cool the apparatus to room temperature. The resulting 1945 g black powder was catalyst material 4.3, with a calcined mass yield of 97%. Catalyst material 4.3 was analyzed by CHN and the results are shown in Table 5.1. Catalyst material 4.3 was subjected to MRU performance testing, the results of which are shown in 5.4.

[0181] [Example 21] Synthesis of catalyst material 4.4 (double washed; no AT) 945 g of catalyst composition 1.6 was calcined to catalyst material 4.4 using the same procedure as outlined for catalyst material 4.3, with the only exception being that only one quartz boat was used instead of two quartz boats due to the smaller amount of material being calcined. After calcination at 600°C for 6 hours under nitrogen, the resulting black powder was catalyst material 4.4, weighing 892 g, which corresponds to a calcination mass yield of 94% (based on the initial mass of catalyst composition 1.6, i.e., the mass before the additional drying step of the ground catalyst at 90°C). Catalyst material 4.4 was analyzed by CHN, the results of which are shown in Table 5.1. Catalyst material 4.4 was also subjected to MRU performance testing, the results of which are shown in 5.4.

[0182] [Example 22] Synthesis of catalyst material 4.5 (V reduction, normal cleaning, no AT) Of the total 6062 g of catalyst composition 1.8, 1040 g (17%) was calcined to catalyst material 4.5 using the same procedure outlined for catalyst material 4.3, with the only exception being that only one quartz boat was used instead of two quartz boats due to the smaller amount of material being calcined. After calcination at 600° C. under nitrogen for 6 hours, the resulting black powder was catalyst material 4.5, weighing 982 g, which represented a calcination mass yield of 94% (based on the initial mass of catalyst composition 1.8, before the additional drying step of the ground catalyst at 90° C.). Catalyst material 4.5 was subjected to MRU performance testing, the results of which are shown in 5.4.

[0183] Analysis of N (wt%) by CHN for catalyst materials 4.3 and 4.4. [Table 16]

[0184] Analysis of the concentration and molar ratio of Mo, V, Nb, and Te by ICP-MS in catalyst material 4.1. [Table 17]

[0185] Catalyst materials 2.1, 3.1 and 4.1 were all generated from a common catalyst composition 1.1, but were worked up in different ways to produce the final catalyst materials. [Table 18] Catalyst materials 2.1, 3.1 and 4.1 were all generated from a common catalyst composition 1.1 but were worked up in different ways to produce the final catalyst materials. The molar ratios were calculated based on the ICP-MS results shown in Table 5.2. The molar ratios are relative to the moles of Mo.

[0186] Analysis of activity and selectivity of catalyst materials 4.1-4.5 from ethane to ethylene. [Table 19]

[0187] Catalyst materials 2.1-2.10 were prepared in amounts less than about 900 g. The results in this table, compared to catalyst materials 2.X (Table 3.6) and 3.X (Table 4.3), illustrate the importance of meeting the S (wt%) specification of less than about 0.02 wt%. As described herein, this can be accomplished for large scale calcined material, e.g., greater than about 1 kg, through air treatment or thorough washing during filtration.

[0188] Exemplary embodiments Exemplary embodiments described in the Examples herein provide a catalyst composition comprising molybdenum, vanadium, tellurium, niobium, and oxygen, wherein the molar ratio of molybdenum to vanadium is from 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.40, the oxygen is present in an amount at least sufficient to satisfy the valence of any metal oxides present, and the composition comprises less than 1.0 wt.% sulfur.

[0189] In one embodiment, the composition comprises less than 0.50 wt.% sulfur. In one embodiment, the composition comprises 0.001 wt.% to 0.90 wt.% sulfur.

[0190] In one embodiment, the composition comprises 0.5% to 3.0% by weight nitrogen. In one embodiment, the composition comprises 0.8% to 2.0% by weight nitrogen. In one embodiment, the composition comprises 0.8% to 1.2% by weight nitrogen.

[0191] In one embodiment, the composition comprises less than 5.0% by weight of water, hi one embodiment, the composition comprises 0.01% to 2% by weight of water.

[0192] In one embodiment, the catalyst composition has a molar ratio of molybdenum to vanadium of from 1:0.12 to 1:0.49, a molar ratio of molybdenum to tellurium of from 1:0.01 to 1:0.30, and a molar ratio of molybdenum to niobium of from 1:0.01 to 1:0.30.

[0193] In one embodiment, the composition is prepared by a process comprising: hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-cleaned composition comprising greater than 0.5 wt. % sulfur; and washing the pre-cleaned composition with a solution comprising a polar solvent to provide a composition comprising less than 0.25 wt. % sulfur.

[0194] In one embodiment, the polar solvent is water.

[0195] In one embodiment, the composition is prepared at a scale of at least 200 g. In one embodiment, the composition is prepared at a scale of at least a kilogram. In one embodiment, the composition is prepared at a scale of about 1 ton to about 5 ton.

[0196] Another exemplary embodiment described in the Examples herein provides a pre-calcined catalyst composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. In the catalyst composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.05 to 1:0.40. The oxygen is present in an amount that satisfies at least the valence of the metal oxides present, and the sulfur, if present, comprises 0.001% to 0.25% by weight of the composition. The composition is prepared by a method comprising hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-washed ODH catalyst precursor comprising greater than 0.5% by weight sulfur, and washing the pre-washed ODH catalyst precursor with a solution comprising water to provide an ODH catalyst precursor comprising less than 1.0% by weight sulfur.

[0197] Another exemplary embodiment described in the examples herein provides a method for preparing a catalyst composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and optionally sulfur. In the catalyst composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.05 to 1:0.40. The oxygen is present in an amount that satisfies at least the valence of the metal oxides present, and sulfur, if present, accounts for less than 0.25 wt.% of the composition. The method includes hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-washed catalyst composition comprising more than 0.5 wt.% sulfur, and washing the pre-washed catalyst composition with a solution comprising a polar solvent to provide a catalyst composition comprising less than 0.25 wt.% sulfur.

[0198] In one embodiment, the polar solvent comprises water.

[0199] In one embodiment, the composition comprises 0.01% to 0.1% by weight sulfur. In one embodiment, the composition comprises 0.8% to 2.0% by weight nitrogen. In one embodiment, the composition comprises 0.8% to 1.2% by weight nitrogen.

[0200] In one embodiment, the method prepares at least 200 grams of the composition. In one embodiment, the method prepares at least 1 kilogram of the composition. In one embodiment, the method prepares about 1 ton to about 5 tonnes of the composition per batch.

[0201] In one embodiment, the method further comprises providing an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium. In one embodiment, providing the aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium comprises providing an aqueous mixture comprising molybdenum; providing an aqueous mixture comprising tellurium; providing an aqueous mixture comprising vanadium; providing an aqueous mixture comprising niobium; and combining the aqueous mixture comprising molybdenum, the aqueous mixture comprising tellurium, the aqueous mixture comprising vanadium, and the aqueous mixture comprising niobium to provide an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium.

[0202] In one embodiment, providing an aqueous mixture comprising vanadium comprises preparing an aqueous mixture from a vanadium compound and water. In one embodiment, the vanadium compound comprises a vanadium compound selected from vanadium acetylacetonate, vanadyl acetylacetonate, vanadyl stearate, vanadium naphthenate, vanadium benzoylacetonate, vanadyl sulfate, or combinations thereof. In one embodiment, the vanadium compound comprises vanadyl sulfate. In one embodiment, the vanadyl sulfate comprises vanadyl sulfate hydrate.

[0203] In one embodiment, providing an aqueous mixture comprising niobium comprises preparing an aqueous mixture from at least niobium pentoxide, an acid, and water. In one embodiment, providing an aqueous mixture comprising niobium comprises preparing an aqueous mixture from at least niobium pentoxide hydrate, oxalic acid, and water. In one embodiment, providing an aqueous mixture comprising tellurium comprises preparing an aqueous mixture from at least telluric acid (Te(OH)6) and water.

[0204] In one embodiment, providing a mixture comprising molybdenum includes preparing an aqueous mixture from at least ammonium molybdate tetrahydrate and water.

[0205] In one aspect, the method includes combining an aqueous mixture comprising molybdenum with an aqueous mixture comprising tellurium to provide an aqueous mixture comprising molybdenum and tellurium; combining an aqueous mixture comprising molybdenum and tellurium with an aqueous mixture comprising vanadium to provide an aqueous mixture comprising molybdenum, tellurium, and vanadium; and combining an aqueous mixture comprising molybdenum, tellurium, and vanadium with an aqueous mixture comprising niobium to provide an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium.

[0206] In one embodiment, the method includes heating the aqueous mixture containing molybdenum and tellurium at a temperature of about 60° C. to about 100° C. In one embodiment, the method includes heating the aqueous mixture containing molybdenum and tellurium at a temperature of about 80° C. In one embodiment, the method includes increasing the pH of the aqueous mixture containing molybdenum and tellurium to about 7.0 to about 8.5. In one embodiment, the method further includes increasing the pH of the aqueous mixture containing molybdenum and tellurium to about 7.25 to about 7.75. In one embodiment, increasing the pH of the aqueous mixture includes combining an aqueous hydroxide solution with the aqueous mixture containing molybdenum and tellurium. In one embodiment, increasing the pH of the aqueous mixture containing molybdenum and tellurium includes combining ammonium hydroxide with the aqueous mixture containing molybdenum and tellurium.

[0207] In one embodiment, the method further comprises lowering the pH of the aqueous mixture comprising molybdenum and tellurium to a pH of about 4.0 to about 6.0. In one embodiment, the method further comprises lowering the pH to a pH of about 4.75 to about 5.25. In one embodiment, lowering the pH of the aqueous mixture comprising molybdenum and tellurium comprises combining sulfuric acid with the aqueous mixture comprising molybdenum and tellurium.

[0208] In one embodiment, the method further includes heating the aqueous mixture containing molybdenum and tellurium to a temperature of from about 70° C. to about 90° C.; increasing the pH of the aqueous mixture containing molybdenum and tellurium to a pH of from about 7.25 to about 7.75; and decreasing the pH of the aqueous mixture containing molybdenum and tellurium to from about 4.75 to about 5.25 prior to combining the aqueous mixture containing vanadium with the aqueous mixture containing molybdenum and tellurium.

[0209] In one embodiment, the method further includes heating the aqueous mixture containing molybdenum and tellurium to a temperature of about 70° C. to about 90° C.; increasing the pH of the aqueous mixture containing molybdenum and tellurium to a pH of about 7.25 to about 7.75; stirring the aqueous mixture containing molybdenum and tellurium for about 0.5 hours to about 24 hours; and lowering the pH of the aqueous mixture containing molybdenum and tellurium to about 4.75 to about 5.25 prior to adding the aqueous mixture containing vanadium to the aqueous mixture containing molybdenum and tellurium to provide an aqueous mixture containing molybdenum, tellurium, and vanadium.

[0210] In one embodiment, the hydrothermal reaction conditions include a temperature of about 145° C. to about 185° C. In one embodiment, the hydrothermal reaction conditions include a temperature of about 160° C. to about 165° C.

[0211] In one embodiment, the hydrothermal reaction conditions include a pressure of about 75 psig to about 125 psig. In one embodiment, the hydrothermal reaction conditions include a pressure of about 95 to about 105 psig.

[0212] In one embodiment, the hydrothermal reaction conditions include a temperature of about 145° C. to about 185° C. and a pressure of about 75 psig to about 125 psig. In one embodiment, the hydrothermal reaction conditions include a temperature of about 160° C. to about 165° C. and a pressure of about 95 psig to about 105 psig.

[0213] In one embodiment, the hydrothermal reaction time is about 12 hours to about 60 hours. In one embodiment, the hydrothermal reaction time is about 24 hours to about 48 hours. In one embodiment, the hydrothermal reaction conditions include a temperature of about 145°C to about 185°C, a pressure of about 75 psig to about 125 psig, and a time of about 12 hours to about 60 hours. In one embodiment, the hydrothermal reaction conditions include a temperature of about 160°C to about 165°C, a pressure of about 95 psig to about 105 psig, and a time of about 24 hours to about 48 hours.

[0214] In one embodiment, the method further comprises filtering the hydrothermal reaction mixture to provide a pre-washed catalyst composition. In one embodiment, washing the pre-washed catalyst composition comprises washing the pre-washed catalyst composition with about 11 liters to about 46 liters of water per kg of the pre-washed catalyst composition. In one embodiment, washing the pre-washed catalyst composition comprises washing the pre-washed catalyst composition with about 24 liters to about 34 liters of water per kg of the pre-washed catalyst composition. In one embodiment, washing the pre-washed catalyst composition comprises washing the pre-washed catalyst composition with about 29 liters of water per kg of the pre-washed catalyst composition.

[0215] In one embodiment, the method further comprises drying the washed catalyst composition. In one embodiment, drying the washed catalyst composition comprises reducing the amount of water in the catalyst composition to less than 5% water by weight of the composition. In one embodiment, drying the washed catalyst composition comprises reducing the amount of water in the catalyst composition to less than 2% water by weight of the composition. In one embodiment, drying the washed catalyst composition comprises reducing the amount of water in the catalyst composition to between 0.01% and 2% water by weight of the composition.

[0216] In one embodiment, the washed catalyst composition is dried at a temperature of about 60° C. to about 330° C. In one embodiment, the washed catalyst composition is dried at a temperature of about 200° C. to about 300° C. In one embodiment, the washed catalyst composition is dried at a temperature of about 250° C. In one embodiment, the washed catalyst composition is dried at a temperature of about 70° C. to about 110° C. In one embodiment, the washed catalyst composition is dried at a temperature of about 90° C. In one embodiment, the washed catalyst composition is dried at a temperature of about 60° C. to about 330° C. for about 1 hour to about 240 hours. In one embodiment, the method further comprises air treatment to provide the catalyst composition.

[0217] In one embodiment, the method further comprises grinding the catalyst composition. In one embodiment, the average particle size of the ground catalyst composition is from about 50 μm to about 1,000 μm. In one embodiment, the average particle size of the ground catalyst composition is from about 125 μm to about 500 μm.

[0218] Another exemplary embodiment described in the Examples herein provides a catalytic material comprising molybdenum, vanadium, tellurium, niobium, and oxygen, wherein the molar ratio of molybdenum to vanadium is 1:0.12 to 1:0.49, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.01 to 1:0.30, the oxygen is present in an amount at least sufficient to satisfy the valence of any metal oxide present, and sulfur, if present, comprises less than 0.01 weight percent of the catalytic material.

[0219] In one embodiment, the molar ratio of molybdenum to vanadium is 1:0.20 to 1:0.45, the molar ratio of molybdenum to tellurium is 1:0.05 to 1:0.25, and the molar ratio of molybdenum to niobium is 1:0.05 to 1:0.25. In one embodiment, the molar ratio of molybdenum to vanadium is 1:0.25 to 1:0.40, the molar ratio of molybdenum to tellurium is 1:0.10 to 1:0.20, and the molar ratio of molybdenum to niobium is 1:0.10 to 1:0.20. In one embodiment, the molar ratio of molybdenum to vanadium is 1:0.30 to 1:0.35, the molar ratio of molybdenum to tellurium is 1:0.13 to 1:0.17, and the molar ratio of molybdenum to niobium is 1:0.12 to 1:0.14.

[0220] In one embodiment, the catalytic material comprises less than 0.005% by weight sulfur. In one embodiment, the catalytic material comprises less than 0.003% by weight sulfur.

[0221] In one embodiment, the catalytic material further comprises 0.01% to 1.0% by weight of nitrogen.In one embodiment, the catalytic material further comprises 0.5% to 0.3% by weight of nitrogen.

[0222] In one embodiment, the catalytic material comprises between 25% and 35% oxygen by weight.In one embodiment, the catalytic material comprises between 27% and 33% oxygen by weight.

[0223] In one embodiment, the catalytic material has a 35% conversion temperature of about 350°C to about 425°C. In one embodiment, the catalytic material has a 35% conversion temperature of about 360°C to about 390°C. In one embodiment, the catalytic material has a 35% conversion temperature of about 370°C to about 380°C. In one embodiment, the catalytic material has a selectivity for ethylene of about 75% to about 95%. In one embodiment, the catalytic material has a selectivity for ethylene of about 80% to about 90%.

[0224] In one embodiment, the catalytic material has the empirical formula Mo 1.0 V 0.12-0.49 Te 0.01-0.30 Nb 0.01-0.30 O d In one embodiment, the catalytic material comprises a mixed metal oxide having an empirical formula of Mo 1.0 V 0.20-0.45 Te 0.05-0.25 Nb 0.05-0.25 O d In one embodiment, the catalytic material comprises a mixed metal oxide having an empirical formula of Mo 1.0 V 0.25-0.40 Te 0.10-0.20 Nb 0.10-0.20 O d In one embodiment, the catalytic material comprises a mixed metal oxide having an empirical formula of Mo 1.0 V 0.30-0.35 Te 0.13-0.17 Nb 0.12-0.14 O d where d is a number that satisfies the valence of the oxide.

[0225] In one embodiment, the catalytic material is prepared by a method comprising providing a catalytic composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur, wherein the molar ratio of molybdenum to vanadium is from 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.40. The oxygen is present in an amount at least sufficient to satisfy the valence of the metal oxide. The sulfur comprises less than 0.25% by weight of the composition. In the method of this embodiment, the catalytic composition is calcined to provide the catalytic material.

[0226] In one embodiment, calcining the catalyst composition comprises heating the catalyst composition at a temperature of about 500° C. to about 650° C. In one embodiment, calcining the catalyst composition comprises heating the catalyst composition at a temperature of about 600° C.

[0227] In one embodiment, calcining the pre-calcined catalyst composition comprises heating the pre-calcined catalyst composition at a temperature of about 500° C. to about 650° C. for about 2 hours to about 24 hours. In one embodiment, calcining the pre-calcined catalyst composition comprises heating the pre-calcined catalyst composition at a temperature of about 600° C. for about 6 hours.

[0228] In one embodiment, providing the pre-calcined catalyst composition includes hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-washed composition comprising greater than 0.5 wt. % sulfur, and washing the pre-washed composition with a solution comprising a polar solvent to provide a pre-calcined catalyst composition comprising less than 0.25 wt. % sulfur.

[0229] In one embodiment, the pre-calcined catalyst composition contains less than 0.1 wt.% sulfur. In one embodiment, the pre-calcined catalyst composition contains less than 1.2 wt.% nitrogen. In one embodiment, the pre-calcined catalyst composition contains less than 5 wt.% water.

[0230] In one embodiment, the catalytic material is prepared at least on a 200 g scale. In one embodiment, the catalytic material is prepared at least on a kilogram scale.

[0231] Another exemplary embodiment described in the Examples herein provides a method for preparing a catalytic material comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. The method includes hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a pre-cleaned composition comprising greater than 0.5% by weight of sulfur. The method includes washing the pre-cleaned composition with a solution comprising a polar solvent to provide a catalytic composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and sulfur. In the catalytic composition, the molar ratio of molybdenum to vanadium is 1:0.05 to 1:0.60, the molar ratio of molybdenum to tellurium is 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is 1:0.01 to 1:0.40. Oxygen is present in the catalytic composition in an amount that at least satisfies the valence of the metal oxides present. Sulfur accounts for less than 0.25% by weight of the composition. The method includes calcining a catalyst composition to provide a catalyst material, wherein the molar ratio of molybdenum to vanadium is from 1:0.12 to 1:0.49, the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30, and the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.30, oxygen is present in an amount at least to satisfy the valences of any metal oxides present, and sulfur, if present, comprises less than 0.01 weight percent of the catalyst material. [Industrial Applicability]

[0232] Catalyst for oxidative dehydrogenation.< / ftir> < / mru>

Claims

1. A catalyst composition comprising molybdenum, vanadium, tellurium, niobium, and oxygen, the molar ratio of molybdenum to vanadium is from 1:0.05 to 1:0.60; the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30; the molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.40; The oxygen is present in an amount to at least satisfy the valence of the metal oxides present, and the composition contains less than 1.0 wt.% sulfur. Catalyst composition.

2. The catalyst composition of claim 1, wherein the composition contains less than 0.50 weight percent sulfur.

3. The catalyst composition of claim 1, wherein the composition contains from 0.001% to 0.90% by weight of sulfur.

4. The catalyst composition of claim 1, wherein the catalyst composition comprises 0.5% to 3.0% by weight of nitrogen.

5. The catalyst composition of claim 1, wherein the catalyst composition comprises from 0.8% to 1.2% by weight of nitrogen.

6. The catalyst composition of claim 1, wherein the catalyst composition comprises 0.01% to 2% by weight of water.

7. the molar ratio of molybdenum to vanadium is from 1:0.12 to 1:0.49; the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30; The molar ratio of molybdenum to niobium is from 1:0.01 to 1:0.

30. The catalyst composition according to any one of claims 1 to 6.

8. The catalyst composition of claim 1, wherein the catalyst composition is prepared on at least a kilogram scale.

9. The catalyst composition of claim 1, wherein the catalyst composition is prepared on a 1 to 5 ton scale.

10. 1. A method for preparing a catalyst composition comprising molybdenum, vanadium, tellurium, niobium, oxygen, and, optionally, sulfur, comprising the steps of: the molar ratio of molybdenum to vanadium is from 1:0.05 to 1:0.60; the molar ratio of molybdenum to tellurium is from 1:0.01 to 1:0.30; the molar ratio of molybdenum to niobium is from 1:0.05 to 1:0.40; oxygen is present in an amount at least sufficient to satisfy the valence of any metal oxides present; and sulfur, if present, constitutes less than 0.25 weight percent of the composition; The method comprises: hydrothermally reacting an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium to provide a prewashed catalyst composition comprising greater than 0.5 wt. % sulfur; and washing the pre-washed catalyst composition with a solution comprising a polar solvent to provide a catalyst composition comprising less than 0.25 wt. % sulfur; A method comprising:

11. The method of claim 10 , wherein the polar solvent comprises water.

12. The method of claim 10 or 11, wherein the catalyst composition comprises from 0.01% to 0.1% by weight of sulfur.

13. A method according to any one of claims 10 to 12, wherein the composition comprises from 0.8% to 1.2% by weight of nitrogen.

14. The process of any one of claims 10 to 13, wherein at least 1 kilogram of the catalyst composition is prepared.

15. The process according to any one of claims 10 to 14, wherein from 1 tonne to 5 tonnes of the catalyst composition are prepared per batch.

16. The method of any one of claims 10 to 15, further comprising providing an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium.

17. Providing an aqueous mixture comprising molybdenum, vanadium, tellurium, and niobium, providing an aqueous mixture comprising molybdenum; providing an aqueous mixture comprising tellurium; providing an aqueous mixture containing vanadium; providing an aqueous mixture comprising niobium; and combining the molybdenum-containing aqueous mixture, the tellurium-containing aqueous mixture, the vanadium-containing aqueous mixture, and the niobium-containing aqueous mixture to provide an aqueous mixture containing molybdenum, vanadium, tellurium, and niobium; 17. The method of claim 16, comprising:

18. 20. The method of claim 17, The method comprises: combining an aqueous mixture containing molybdenum with an aqueous mixture containing tellurium to provide an aqueous mixture containing molybdenum and tellurium; heating an aqueous mixture containing molybdenum and tellurium to a temperature of from 70° C. to 90° C.; increasing the pH of the aqueous mixture containing molybdenum and tellurium to a pH of 7.25 to 7.75; and reducing the pH of the aqueous mixture containing molybdenum and tellurium to a pH of 4.75 to 5.25; combining an aqueous mixture containing molybdenum and tellurium with an aqueous mixture containing vanadium to provide an aqueous mixture containing molybdenum, tellurium, and vanadium; and combining an aqueous mixture containing molybdenum, tellurium, and vanadium with an aqueous mixture containing niobium to provide an aqueous mixture containing molybdenum, vanadium, tellurium, and niobium; The method further comprising:

19. The method of any one of claims 10 to 18, wherein the filtered catalyst precursor is washed using from 11 liters to 29 liters of solution per kg of filtered catalyst precursor.

20. The process according to any one of claims 10 to 19, wherein the washed catalyst composition is dried at a temperature of from 200°C to 300°C.